From embryo to sexual maturity: chronic BPA exposure under elevated contamination scenarios induces multi-organ toxicity in marine medaka (Oryzias melastigma) - Yangmei Li; Zhang Huan; Qin Lin; Junyi Liu; Wenyang Xiao; Ning Zhang; Zailiang Li; Yanping Zhang; Yusong Guo; Zhongduo Wang; Zhongdian Dong (Marine Pollution Bulletin, 2026)

Numerical analysis of downwash airflow distribution from multi-rotor UAV in soybean-maize strip intercropping canopy - Xinghua Liu; Lei Yang; Yang Li; Zhi Li; Fan Jiang; Yanping Tian; Xiang-Dong Li (Biosystems Engineering, 2026)

Molecular fingerprinting of biodegradable poly(butylene adipate-co-terephthalate) leaching and toxic effects on coastal phytoplankton - Yanping Li; Yan Wang; Ke Pan; Wen-Xiong Wang; Neng Yan (Water Research, 2026)

Screening, characterization and calcium-binding properties of novel yak milk peptides - Bo Zhao; Xinyi Li; Yanping Guo; Wenting Li; Torkun Mamet; Nidhi Bansal (International Dairy Journal, 2026)

Genome-resolved characterization of candidate thermotolerance traits and predicted protein conformational behavior in Calditerricola during hyperthermophilic composting of organic wastes - Xu Li; Zhengnan Zhu; Youzhao Wang; Yanping Zhang; Xiaoyan Dang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Bioresource Technology, 2026)

Phase-based classification of the diurnal cycle of summer precipitation over Northwest China and its coupling with topography - Zixing Kang; Ya Huang; Yanping Li; Dingjia Ye; Guiping Li (Atmospheric Research, 2026)

Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Integrating genomic evolution and reported outbreak occurrence in foot-and-mouth disease in Asia: Cross-border lineage connectivity and exploratory prediction of reported outbreak occurrence - Xiaoyu Ge; Yize Li; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Upcycling lignocellulosic biomass using a radial-axial fixed-bed ex-situ catalytic pyrolysis reactor - Fuzheng Li; Jinping Guo; Xingshan Shi; Weiling Piao; Cristina Franch; Yanping Chen; K. Seshan; Songbo He (Bioresource Technology, 2026)

Study on dynamic response and damage mechanism of tunnel across reverse fault based on different earthquake action modes - Rui Sun; Xiaojun Li; Yanping Yang; Ren Deng; Teng Li; Dingding Xiong (Tunnelling and Underground Space Technology, 2026)

The Scaling Law in remote sensing mapping for model performance forecasting and reference sample optimization - Yuanhong Liao; Yuqi Bai; Shuang Chen; Jie Wang; Yanping You; Zhou Chen; Haoru Wu; Huabing Huang; Wenrui Li; Mingrun Zang; Zimeng Wang; Xinan Zhang; et al. (Remote Sensing of Environment, 2026)

Effects of different morphologies of CeOₓ on the unsaturated Mn/Co defects of MnOₓ/CoOₓ catalysts for highly active photothermocatalysis of acetone and NO - Siqi Jiang; Sihan Li; Yinming Fan; Yanping Zhang; Shengpeng Mo; Lei Liao; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Plasma technology regulated In3S4 nanosheets surface cationic defects enhanced photocatalytic H2O2 production in pure water - Fei Li; Yang Zhang; Yongjie Zhou; Yanping Gao; Longkai Pan; Chen Sun; Hequn Yang; Fei Rao; Gangqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Selective recovery of nickel from spent FCC catalysts using a bio-electrochemical coupled system: The synergistic role of organic acids and Eh-pH regulation - Daoqing Liu; Qianwei Li; Hao Liu; Yanping Zhu; Chunmao Chen (Journal of Environmental Chemical Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Energy window-guided molecular adsorbent for highly selective cesium capture: Breaking the Rb+/Cs+ separation bottleneck - Yanping Wang; Dezhen Fang; Kexin Li; Xiushen Ye; Wenjie Han; Pengrui Zhang; Zhijian Wu; Guosheng Shi; Haining Liu (Chemical Engineering Journal, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Preparation of the Fe3O4@UIO-66-NH2 for the Removal of Water Pollutants by One-step Method - Meizhi Zhang; Yi Ren; Yutong Wang; Cong Wang; Yanping Li (Water, Air, & Soil Pollution, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Salinity reduces cadmium bioavailability and toxicity in the Oryzias melastigma: Evidence from fish exposure and cell-based ion-competition assays - Zhongdian Dong; Jinghua Wang; Haozhong Tian; Jiahao Gao; Yue Liu; Nengneng Ding; Yiqing Yuan; Guohua Zhu; Xiaomin Zhao; Zailiang Li; Ning Zhang; Yanping Zhang; et al. (Marine Pollution Bulletin, 2026)

Measuring and enhancing urban water supply resilience: A dynamic coupling framework and its application in Beijing - Yanping Liu; Jiahua Wei; Minglei Hou; Jiaqi Xu; Chenfei Yan; Li Xue (Sustainable Cities and Society, 2026)

Habitat-dependent and asymmetric drivers of spectral diversity–biodiversity relationships in temperate grasslands - Yi Zhang; Yujin Zhao; Zhisheng Wu; Yanping Zhao; Wenhe Chen; Weifang Li; Zhaoju Zheng; Fei Li; Yongfei Bai (Remote Sensing of Environment, 2026)

SLC6A8-centered placental molecular signature predicts fetal growth restriction via machine learning and single-cell analysis - Qing Hua; Xiaoyan You; Xujing Yan; Yanping Xin; Dongmei Zhang; Xiaona Tian; Li Li (Reproductive Biology, 2026)

Upcycling waste glass into chitosan-modified zeolite for heavy metal immobilization and deep mineralization: A "waste-treats-waste" paradigm - Xinxin Li; Rongxin Guo; Zhihan Zhang; Yifeng Zou; Ziyi Yang; Dexun Zou; Yanping Liu (Process Safety and Environmental Protection, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Short-range and long-range charge transfer based narrowband deep blue organic fluorescence emitters with EQE > 20% and CIEy ≈ 0.04 - Wenyan Zhao; Zijian Chen; Jihua Tan; Zhenyue Duan; Danhong Zhou; Yanping Huo; Jiuyan Li; Ruifang Wang; Pengzhong Chen; Xiaojun Peng (Chemical Engineering Journal, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Folding integrated all-paper photoelectrochemical immunoassay using annealed ZnO for point-of-care detection of ferritin - Yibin Cai; Haining Li; Yanping Chen; Shuyi Lu; Huanhuan Zhu; Dianping Tang; Xiao Han; Shaofeng Lin (Analytica Chimica Acta, 2026)

Dual-ion synergistic biopolymer hydrogel: Efficient acid blue 113 adsorption with algal safety - Yanping Jia; Shuo Li; Yaoxin Hu; Jian Zhang; Fei Du; Ruixuan Cai; Lanhe Zhang (Journal of Water Process Engineering, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Response mechanisms of enhanced biological phosphorus removal systems to microplastics stress - Mingwan Yang; Li Tian; Qihao Li; Guijie Li; Lulu Dai; Anni Du; Liguan Li; Ke Yu; Yanping Mao (Journal of Hazardous Materials, 2026)

Synergistic effects of ultrasound-assisted freezing and NADES on the cryostability of surimi gel: Perspective of quality and molecular structure - Yue Chen; Xindi Zeng; Yanping Wang; Xinyan Li; Xin Du; Xiufang Xia (Food Chemistry, 2026)

GmHMGR6 enhances salt stress tolerance in soybean through modulation of nitrogen metabolism - Xinjie Feng; Hongzhen Liu; Yingyue Zhang; Yanping Li; Zhengxing Guo; Rong Bao; Xiuli Zhang; Xinying Liu; Huihui Zhang (Plant Cell Reports, 2026)

Molecular Analysis of a New Alphapartitivirus from Rhizoctonia solani AG-4 HG III Isolate Rs292 - Yangyang Li; Yanping He; Hongyang Chu; Wenli Li; Hongyu Wang; Yi Chen; Churong Wu; Yanqiong Li (Current Microbiology, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Sleep Duration and Epilepsy Risk: Mendelian Randomization and Functional Validation of CACNA1A rs2228130-Related Inhibitory Synaptic Dysfunction - Xun Li; Yuying Hou; Yanping Ren; Wei Yue (NeuroMolecular Medicine, 2026)

Robot-assisted laser osteotomy system based on dose–effect model-guided feedforward control - Zeng Kuang; Yanping Lin; Shiqi Peng; Yinwei Li; Huifang Zhou (Medical & Biological Engineering & Computing, 2026)

Lipopolysaccharide promotes rheumatoid arthritis by enhancing Wnt7b mediated macrophage-FLS communication - Bing Wang; Yingqiu Song; Wenbo Xu; Jiaqing Chen; Yurong Huang; Xinyue Zhou; Yikang Cai; Aixin Xia; Yanping Li; Liwei Jiang; Faxue Liao; Jian Huang; et al. (Inflammation Research, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Molecular mechanism by which high temperature and RecBCD synergistically lower strand-separation barriers and promote destabilization of representative efflux-pump ARG fragments (macB/tetA) during hyperthermophilic composting - Xu Li; Youzhao Wang; Xiaoyan Dang; Yanping Zhang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Antagonistic modulation of myosin conformational dynamics by sanshool and smoke-derived aldehydes: A molecular basis for heterocyclic amine control in thermal processing - Hongyu Deng; Jie Jia; Lihui Feng; Siwei Xiong; Hemei Yuan; Zhiyuan Fang; Qiulan Li; Shengjie Duan; Hongkang Zhu; Ya Wang; Jun Sheng; Yanping Huang; et al. (Food Chemistry, 2026)

Mining and characterization of endogenous constitutive promoters in Aspergillus oryzae - Sha Huang; Laimao Luo; Jingyin Zhou; Zhui Tu; Qinhua He; Yanping Li (Food Bioscience, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Urban Cooling Island Dynamics During the Development of an Ecological Urban Agglomeration in China - Ziwu Pan; Zunyi Xie; Lifei Huang; Fen Qin; Minmin Yu; Shuyu Yang; Zihan Wang; Jinyuan Han; Zenyan Wang; Yanping Cao; Zhihua Shi; Cangyu Li (Chinese Geographical Science, 2026)

Port-city environmental synergy and its impact on urban economic competitiveness: toward sustainable development in China’s eastern coastal regions - Xiaoyue You; Yanping Tian; Zhenqiang Li (Environment, Development and Sustainability, 2026)

The PorV protein as a cross-protective antigen against Riemerella anatipestifer infection - Sen Li; Yanhua Wang; Xiong Liu; Keke Ren; Yanping Deng; Yuncai Xiao; Sishun Hu; Zili Li; Hongbo Zhou; Zhengfei Liu; Zutao Zhou (Veterinary Microbiology, 2026)

Achieving 99% selective photocatalytic conversion of CO2 to CH4 via built-in electric field guided S-scheme charge transfer in UiO-66/CuS heterojunction - Jia Shi; Xiaoqing Shi; Linping Li; Kezhen Lai; Yanping Qiu; Ning Li; Yangqin Gao; Lei Ge (Chemical Engineering Journal, 2026)

Integrative metabolomic and transcriptomic analyses reveal coordinated variation in phenolic acid metabolism and redox-related traits in Ocimum basilicum accessions - Jingtian Yang; Zhengqiao Liao; Jialin Li; Mei Liu; Yanping Mao; Guoyu Yang; Lei Liu (Planta, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

E3 ubiquitin ligases in plant defense: mechanisms and prospects for resistance breeding - Yuansheng Wu; Zhengbao Tao; Zheng Qin; Yanping Li; Minkai Zhao; Shanshan Zhao; Jianguo Wu (Science China Life Sciences, 2026)

Harnessing molecularly imprinted polymers for multiplex detection of emerging contaminants in foods: advances and future perspectives - Quanbin Fu; Yanping Pei; Wenming Liu; Xin Sun; Peng Wu; Houshen Li; Shiyun Ai (Critical Reviews in Food Science and Nutrition, 2026)

Genetic Basis of α-1,3 Galactose Epitopes in Animal Reservoirs of Coronaviruses - Xinjia Mai; Chenxi Zhu; Yu He; Nian Wang; Yue Ma; Wen Zhang; Yanping Wang; Yunsen Li; Dapeng Zhou (Phenomics, 2026)

Optimal management of co-location marine activities in three-dimensional space: A Stackelberg game-based framework - Shuo Wang; Jiaju Lin; Chao Liu; Yanping Li; Saiya Xu (Ocean & Coastal Management, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Study on multiscale particle motion characteristics in hydraulic lifting pipe under pulsating flow conditions - Desheng Chen; Geng Li; Wenhao Sun; Yuanming Ding; Zhe Lin; Yanping Wang (Ocean Engineering, 2026)

Recyclable standardized sludge for performance evaluation of low-temperature drying units: Preparation and feasibility verification - Yuting Qin; Yanping Guo; Yongyou Hu; Jingyu Liu; Guanying Huang; Guanghuan Li; Haochun Chen; Qingying Huang (Journal of Environmental Management, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Evolution of carbon sink patterns and spatial planning suitability in the Qingdao Coastal Zone based on the coupled InVEST–PLUS model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Zhiwei Zhang; Yanping Li; Zheng Li (Frontiers in Marine Science, 2026)
To support the “dual-carbon” strategy and develop a carbon-sink-oriented coastal spatial planning framework, this study applies the coupled InVEST–PLUS model to Qingdao using 30 m resolution land-use data. Six spatial drivers (DEM, slope, GDP, population, road, and water proximity) are used to simulate land-use change and evaluate its impact on carbon storage. Model validation results indicate that the PLUS model shows good performance (Kappa ≈ 0.79, FoM = 0.168). The results indicate that (1) during 2010–2020, land-use patterns in the study area changed markedly, characterized by a decrease in farmland and an expansion of architecture area, while forest increased slightly and overall ecological land declined. (2) Total carbon storage dropped from 5.3174 × 10 7 t (2010) to 5.2749 × 10 7 t (2020), with a net loss of 4.25 × 10 5 t. Spatially, carbon storage showed a “clustered-high, contiguous-medium, radial-low” pattern. (3) DEM and water proximity primarily drove the expansion of farmland, forest, grassland, and waters, while population density and DEM dominated architecture growth; bare land expansion was mainly driven by population. Based on these findings, carbon storage transfer pathways are quantified, providing a scientific basis for low-carbon-oriented territorial spatial governance in coastal zones.

Oyster aquaculture enhances sedimentary nitrogen removal in a subtropical estuary - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Xin Luo; Dost Muhammad; Shahzad Afzal; Ke Pan (Regional Studies in Marine Science, 2026)

Sequential multi-objective maintenance optimization with dynamic importance ranking: A case study of subsea transportation system - Yixin Zhao; Baoping Cai; Yiliu Liu; Yanping Zhang; Shibo Wu; Gan Li (Ocean Engineering, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Light-driven decontamination of co-existing organic pollutants by Zn3In2S6/ZnWO4 heterojunction: Degradation behavior and mechanisms - Qian Xiao; Shijie Li; Bing Leng; Zuofang Yao; Zebin Yu; Chenchen Xing; Boge Zhang; Xiaoyu Tong; Yanping Hou (Journal of Environmental Chemical Engineering, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Evaluating microphysics scheme impacts on summer precipitation in Northwestern China using a convection permitting WRF model - Ya Huang; Qingyun Duan; Yong Zhao; Lihua Chen; Yanping Li (Atmospheric Research, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Phloretin enhances the efficiency of sheep oocyte IVM and early embryonic development by bolstering antioxidant defenses, inhibiting apoptosis, and promoting development - Xu Li; Shuhong Tang; Yinwei Zheng; Ruiguo Zhao; Feifan Xu; Naerhulan Ayiken; Guangdong Hu; Yanping Wang; Weibin Zeng (Reproductive Biology, 2026)

Microwave-assisted regeneration of CuxO-modified activated carbon saturated with sulfamethazine: Mechanism and performance evaluation - Yanping Liu; Zixiu Li; Dandan Liu; Mingjie Han; Jianfeng Gao; Haoyu Zou (Process Safety and Environmental Protection, 2026)

Pa-miR396 targets PaGRFs to disrupt PaGRF–PaGIF transcriptional activation in Platanus acerifolia leaf development - Yongkang Lu; Yuqing Chen; Dasui Li; Manzhu Bao; Yanping Zhang (Plant Science, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

A comprehensive assessment of VOCs from multi-story swine farms: Sources, mitigation, and integrated risks - Dongxuan Han; Xue Li; Xiaojie Yan; Shuijiang Fu; Xin Li; Yanping Li; Bin Zhou; Kaiying Wang (Journal of Environmental Management, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Immunoenhancing Effect of Lactobacillus Kefiranofaciens ZW18 Postbiotic On Cyclophosphamide-induced Immunosuppressed Mice - Hanxue Xu; Xinyuan Li; Weitao Geng; Longgang Jia; Yanping Wang; Jinju Wang (Probiotics and Antimicrobial Proteins, 2026)

Genome characterization of a novel chrysovirus infecting Aspergillus Niger - Li Wang; Futao Huang; Jia Mi; Changfeng Long; Yelin Xu; Xiaolan Qi; Yanping Jiang; Tom Hsiang; Yinhui Jiang (Archives of Virology, 2026)

Assessing Coastal Ecological Restoration Effectiveness in Qingdao Based on a Multi-Dimensional Entropy-Weighted TOPSIS Model - Chunxia Xu; Chunjuan Wang; Dahai Liu; Yanping Li; Chao Liu; Zheng Li (Journal of Marine Science and Engineering, 2026)
Coastal ecological restoration is a key approach to enhancing ecosystem resilience; however, the stage-wise evolution of restoration outcomes and the underlying driving mechanisms remain insufficiently quantified. Using Qingdao City as the study area, this research integrates remote sensing inversion, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, and time-series data from 2010 to 2020 to develop a comprehensive evaluation system for ecological restoration effectiveness, comprising 17 indicators across five dimensions: vegetation, biology, hydrology, economy, and climate. Based on this system, the entropy-weighted method is applied to conduct a dynamic assessment of restoration outcomes. The results indicate that (i) the composite evaluation score in the study area decreased from 0.36 in 2010 to 0.19 in 2015 and then increased to 0.74 in 2020, forming a “V-shaped” nonlinear trajectory with 2015 as a turning point, which is temporally consistent with a delayed response of ecological restoration outcomes following the implementation of major anthropogenic interventions. (ii) Dimension-specific analysis indicates that the decline in the composite score during 2010–2015 was mainly associated with the hydrological dimension, within which chemical oxygen demand (COD) and ammonia nitrogen emissions showed marked increases and were among the highest-weighted indicators. After 2015, following the intensive implementation of regional and system-oriented restoration projects such as the Blue Bay Initiative, pollutant emissions were observed to be effectively controlled, and Bare land area showed a continuous decline. These changes coincided with the rapid rebound of the composite score, within which Bare land area, as the highest-weighted indicator, played a prominent regulatory role. Marked differences were observed among dimensional responses: the biological and vegetation dimensions showed sustained improvement throughout the study period, whereas the hydrological dimension exhibited greater variability over time and stronger temporal alignment with policy-related phases. (iii) Robustness tests indicate that, after completely excluding climate-related variables, the composite score still increased from 0.36 and 0.24 to 0.77, with the “V-shaped” recovery pattern remaining unchanged. This result suggests that the observed improvement in restoration effectiveness in 2020 was more closely associated with systematic human interventions, rather than with short-term climatic fluctuations. This study provides a quantitative and transferable methodological framework for the dynamic evaluation and stage-oriented analysis of coastal ecological restoration effectiveness.

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Macrobenthic community dynamics inform mangrove restoration practices for China - Yiyong Rao; Danyi Li; Fengxia Wu; Lizhe Cai; Shufei Zhang; Huaxue Liu; Yanping Zhong; Honghui Huang (Ocean & Coastal Management, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Deciphering the spatiotemporal dynamics and source characteristics of nutrients under anthropogenic pressure in Taipu River, China - Tong Wang; Jiayi Kou; Fengjunxi Chen; Yalong Li; Yaojen Tu; Yanping Duan (Journal of Contaminant Hydrology, 2026)

Solar-driven degradation of HEDP and simultaneous phosphorus recovery from electroplating wastewater via a Cu (III)-mediated biochar electro-Fenton system - Shibo Zhao; Yanping Cui; Qiao Huang; Xian Xiang; Yuqing Qu; Chu Xiong; Bolin Li; Caixia Wen (Chemical Engineering Journal, 2026)

Pou4f3 Deficiency Obstructs the Subtype Differentiation of Vestibular Hair Cells - Qin Zhou; Yikang Huang; Wenli Ni; Mingchuan Feng; Lingjie Wu; Chuijin Lai; Yanping Zhang; Wenyan Li; Yan Chen (Neuroscience Bulletin, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

Improving slurry flow predictions in horizontal pipes: A modification to the Burns turbulent dispersion force model - Weihuang Liu; Yanping He; Mingzhi Li; Hongbo Zhu; Minmin Zheng (Ocean Engineering, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Breaking the cycle of resistance: Hyperthermophilic composting establishes a multi-layered defense against ARG dissemination - Xu Li; Yanping Zhang; Chaoyue Zhao; Xiaoyan Dang; Bingzhen Li; Shujie Hou; Xiaolong Gao; Jiedong Hao; Zhenning Lyu; Youzhao Wang; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Fungal communities dominate accumulation of microbial necromass carbon after 11-year revegetation in a semi-arid desert mining area - Pengfei Li; Wenjiang Fu; Yiwei Bai; Daren Zhou; Shiqi Sun; Qiao Guo; Jianguo Zhang; YanPing Miao; Hangxian Lai (Journal of Environmental Management, 2026)

CoOOH-based colorimetric aptasensor with dual cascade amplification for ultrasensitive monitoring of fleroxacin in honey - Yanping He; Peixuan Li; Xin Zhao; Dongmei Wang; Fuqiang Zhang (Food Control, 2026)

Grass roots on gully bed inhibit plunge pool development but have a limited influence on headcut retreat: a case study based on an in-situ experiment in dry-hot valley of southwest China - Yanping Liu; Yifan Dong; Jie Feng; Ronghua Zhong; Li Rong (CATENA, 2026)

Targeting Phospholipid Metabolism as an Effective Hearing Protection Strategy - Huanyu Mao; Wenli Ni; Lupeng Ma; Xiang Li; Yanping Zhang; Yuzheng Zhao; Wenyan Li; Huawei Li; Yan Chen (Neuroscience Bulletin, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Unvegetated Tidal Flats: A Critical Yet Vulnerable Coastal Blue Carbon Sink - Yanping Wang; Changchun Li; Zhaoliang Peng; Jing Luo; Senlin Zhu; Yumeng Sun; Ruping Liu; Dongcheng Jiang; Xiangqian Zhou; Faming Wang (Global Change Biology, 2026)
Unvegetated tidal flats, despite accounting for approximately 24.9% of global blue carbon ecosystem area, remain underrepresented in blue carbon budgets. Here, we synthesize data from 184 sites across 23 countries to quantify their carbon stocks, carbon accumulation rate (CAR) and greenhouse gas (GHG, CO 2 and CH 4 ) emissions. Our results reveal that tidal flats sequester 8.6 (4.5–9.9) Tg C yr −1 and store 1.2 (0.7–2.0) Pg C in the top meter of sediments, increasing global blue carbon estimates by 6%–17%. However, they simultaneously emit 0.073 Tg CH 4 yr −1 (3.3 Tg CO 2 eq yr −1 ), 27.9% of the CH 4 emissions from salt marshes, offsetting 14.1% (1.8%–20.4%) of their carbon sequestration benefits. Mudflats exhibit the highest carbon stocks and CO 2 fluxes among different sediment types, primarily due to their abundant binding sites of fine‐grained particles and stronger microbial activities. Both CAR and CH 4 fluxes decline poleward, with tropical zone as hotspots. Our findings highlight the urgency of integrating tidal flats into climate mitigation strategies, particularly given their vulnerability to land‐use changes and sea‐level rise. Conservation efforts must balance carbon sequestration gains against CH 4 trade‐offs to optimize their climate regulation potential.

A Novel, Dual-Response Chemosensor Based on Ferrocene Derivative for the Selective Detection of Al3+ Ions : Fluorescence and Electrochemical Signaling - Wenqin Liu; Yanping Liu; Zenghui Li; Santai Zou; Pingnan Wan; Yan Lin (Journal of Fluorescence, 2025)

Rhizosphere drives microbial necromass carbon accumulation via enhanced carbon use efficiency: Evidence from a common garden experiment - Beibei Wang; Kun Yan; Chao Ji; Kun Li; Yanping Wang; Qitong Wang (Rhizosphere, 2025)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Improvement of electron transfer via anthraquinone-2-sulfonate addition to enhance volatile fatty acids production in anaerobic digestion system - Xiaoyue Li; Tingting Jiang; Huiyan Jing; Yue Cui; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2025)

Performance and mechanism of Co-MOF@BiVO4 sol-gel/graphite felt cathode for antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Xi Li; Naif Abdullah Al-Dhabi; Zuofang Yao; Songyu Fan; Chenchen Xing; Yujia Liu; Hongxiang Zhu; Wangwang Tang; Yanping Hou (Journal of Environmental Chemical Engineering, 2025)

Hydroxylamine enhanced Fe(Ⅱ)-activated peracetic acid process to promote short-chain fatty acid production during sludge anaerobic fermentation - Jing Zhang; Yanping Zhang; Junliang Dong; Fen Li; Zhenjie Guo; Yibing Li (Journal of Environmental Chemical Engineering, 2025)

Environmentally relevant low metal concentrations drive co-selection of antibiotic and metal resistance genes in activated sludge - Li Tian; Guijie Li; Liguan Li; Mingwan Yang; Huixin Li; Qihao Li; Yanping Mao (Environmental Research, 2025)

Ammonium-activated peracetic acid for enhanced tetracycline degradation: Performance and mechanism - Qiao Huang; Yanping Cui; Bolin Li; Chu Xiong; Xian Xiang; Yuqing Qu; Shibo Zhao; Caixia Wen (Environmental Research, 2025)

Fabrication of a nonwoven fabric-based multifunctional mulch film with Cr(VI) remediation capacity - Dongqing Cai; Jinjing Xu; Jiangshan Li; Xianghai Kong; Maowei Wu; Yan Wang; Wanji Zhu; Pan Zhao; Xiaofeng Lu; Xiaoli Tang; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2025)

Superior energy storage and charge-discharge performance achieved in (Pb1-3/2La )(Hf0.9Sn0.1)O3 antiferroelectric ceramics - Shuifeng Li; Xiaobin Guo; Zhenhua Tang; Xin-gui Tang; Qijun Sun; Yanping Jiang; Wenhua Li; Qiuxiang Liu (Chemical Engineering Journal, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Population pharmacokinetic characteristics of tacrolimus in Chinese lung transplant recipients and optimisation of dosing regimen during the early post-transplantation phase - Shouning Zhou; Qiaoyan Lian; Huilong Luo; Hui Xie; Yanping Guan; Jianxing He; Li Wei; Chunrong Ju (European Journal of Clinical Pharmacology, 2025)

Erratum to: Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

A potent and selective PROTAC degrader of CDK9 as effective inhibitor of HIV-1 RNA synthesis - Bo Yang; Ling Ma; Xiaotang Yang; Jiajia Wen; Weiyi Yin; Siqi Li; Yingjie Ji; Ying Wang; Shan Cen; Yanping Li (Molecular Diversity, 2025)

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Mechanistic insights into co-culture inhibition of pellicle formation in fermented chili peppers by Pediococcus ethanolidurans M1117 - Yumeng Li; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Baiyi Lu; Hong Gao (International Journal of Food Microbiology, 2025)

Inhibitory effect of licochalcone A on dual-species biofilms of Listeria monocytogenes and Staphylococcus aureus: mechanism involved in quorum sensing and application in beef - Ling Jiang; Yilin Han; Xianxuan Li; Kai Zhong; Yanping Wu; Hong Gao (International Journal of Food Microbiology, 2025)

Effect of different aroma types of baijiu on the quality of Sichuan paocai - Lihui Huang; Ling Li; Lianqun Wu; Huan Guo; Yanping Wu; Kai Zhong; Hong Gao (Food Chemistry, 2025)

Naringenin attenuates Mandarin fish ranavirus (MRV)-induced hyperinflammation through the inhibition of MAPK and NF-κB signaling pathways - Ziye Zhang; Yanping Ma; Xinru Gao; Chaojiao Hu; Le Hao; Huijie Lu; Yugu Li; Zhenxing Liu (Fish & Shellfish Immunology, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Formation of N-doped carbon nanosheets encapsulated hollow Co1/3Fe2/3P nanocrystals via the nanoscale Kirkendall effect as anode for superior alkali-ion batteries - Xijun Xu; Suping Chen; Fangkun Li; Panpan Zhang; Yanping Huo; Jun Liu (Chemical Engineering Journal, 2025)

Quaternized chitosan/Salvianolic acid B multifunctional hydrogel with ROS/glucose dual responsive properties for diabetic wound healing - Yanping Li; Xin Wang; Chenjiao Miao; Miao Song; Zheng Cao (Carbohydrate Polymers, 2025)

A multivariate framework for assessing propagation thresholds from meteorological to hydrological drought across indus river Basins-South Asia - Irfan Ullah; Xin-Min Zeng; Sidra Syed; Jiefeng Wu; Xiaoye Yang; Shadab Syed; Ning Wang; Yanping Li (Stochastic Environmental Research and Risk Assessment, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

MSSI: a multi-scale shift-invariant metric learning network for visible and long-wave infrared image patch matching - Xiuwei Zhang; Yanping Li; Zhaoshuai Qi; Yue Liang; Yi Sun (International Journal of Remote Sensing, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Honeycomb-like slow-release fertilizer based on drinking water treatment sludge - Yanping Zhu; Shaofeng Dun; Yajuan Li; Tao Zhang; Xianghai Kong; Xiaomeng Han; Shihu Shu; Dongfang Wang; Weigang Wang; Cun Jiang; Kaili Li; Dongqing Cai (Journal of Environmental Chemical Engineering, 2025)

Bioaugmentation with Caldibacillus thermoamylovorans improved methane production of thermophilic anaerobic digestion via enhancing hydrolysis and acidification processes - Mengyao Xiao; Na Wang; Lin Xu; Dongqing Cai; Yanping Zhu; Jiping Shi; Siying Zhang; Li Liu (Journal of Environmental Chemical Engineering, 2025)

The latest advances on the formation, exposure level and control strategies of nitrosamines in meat, poultry and fish products - Minting Guo; Yanping Xian; Xiaojuan Zhao; Min Qian; Jun Li; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

Homogeneous bioluminescent immunosensor for aflatoxin B1 detection via unnatural amino acid-based site-specific labeling - Mengna Chen; Yanping Li; Qinghua He; Junjie Zeng; Xiaojiang Li; Zhui Tu (Food Control, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Ultrasound-triggered piezocatalytic MOF(Hf)-Pt nanozymes for efficient ROS scavenging in the treatment of osteoarthritis - Yi Yao; Zixin Gao; Zhongjie Pan; Yanping Zhong; Lili Qin; Kexin Zhao; Shuhan Liu; Shengqing Zhang; Haoyang Han; Feiying Yin; Ruizheng Liang; Jinmin Zhao; et al. (Chemical Engineering Journal, 2025)

High entropy relaxation ferroelectric ceramics with strong coupled achieved by framework structure guided design and grain boundary optimisation - Renkai Zhao; Kaijie Chen; Wenhua Li; Xingui Tang; Zhifei Jian; YongXi Liang; Jiayi Yin; Yanping Jiang; Xiaobin Guo; Kai Yan (Chemical Engineering Journal, 2025)

Metabolic engineering of a high-light tolerant cyanobacterium Synechocystis sp. PCC 6803 for efficient biosynthesis of β-farnesene from CO2 - Wei Zhang; Jie Zhou; Yanping Zhang; Yin Li (Systems Microbiology and Biomanufacturing, 2025)

Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Electron beam/persulfate-induced second-scale upcycling of wastewater polyvinyl alcohol with ultra-low chemical input - Tao Zhang; Yanping Zhu; Yongle Yu; Xiaoya Pan; Pan Zhao; Shihu Shu; Dongfang Wang; Jiping Shi; Li Liu; Weijian Zhang; Bin Huang; Xiaofeng Lu; et al. (Water Research, 2025)

Resveratrol inhibits autophagy in cardiomyocytes subjected anoxia/reoxygenation injury: involved in VDAC1/PINK1/Parkin pathway - Ying Zhou; Yongzhe Huang; Haiyan Liang; Xiaomei Yang; Shulin Zhang; Yinru Huang; Yanping Wan; Hangfei Zhou; An Huang; Yue Chen; Xiao Li; Yian Peng; et al. (Toxicology and Applied Pharmacology, 2025)

Towards targeted heat resilience: A conceptual framework of urban heat-proof in Chengdu, China - Yutong Li; Sining Zhang; Xiaopeng Li; Shixian Luo; Qingling Liu; Yanping Zhong; Sheng Liu (Sustainable Cities and Society, 2025)

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Enhanced Sb(V) removal from sulfate-rich wastewater by anaerobic granular sludge: Role of AQS-loaded iron sludge-derived hydrochar - Qi Li; Yanping Zhu; Xiong Zheng; Yinguang Chen; Hongying Yuan; Nan Jiang; Mengying Yan; Manhong Huang (Journal of Water Process Engineering, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Functional integrated in gel polymer electrolytes: A handy approach for achieving superior wide temperature range operation sodium metal batteries - Yubin Liao; Fangkun Li; Yadong Zhou; Xijun Xu; Hangyu Zhang; Weizhen Fan; Yanxue Wu; Jingwei Zhao; Jun Liu; Yanping Huo (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Inhibition of tRF- 02514 in Extracellular Vesicles Preserves Microglia Pyroptosis and Protects Against Parkinson’s Disease - Xiaolin Dong; Qingyun Li; Rui Li; Yanping Li; Furong Jin; Hongmei Li; Kun Tu; Gang Wu (Molecular Neurobiology, 2025)

Performance of an integrated modeling framework for spring wheat yield simulation in Saskatchewan, Canada - Qi Zhao; Fei Huo; Yanping Li; Zhenhua Li; Lina Wu (Agricultural and Forest Meteorology, 2025)

Enhanced therapeutic efficacy of Dioscorea cirrhosa Lour. n -butanol fractions in ulcerative colitis: a dual administration approach with comprehensive mucosal protection and anti-inflammatory effects - Mei Wang; XingJu Peng; CanJiao Yang; XinLong Yu; HaiChuan Tai; YanPing Li (Natural Product Research, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Variations in Central Asian dust activity and potential driving mechanisms over the past 80 kyr - Haoru Wei; Yougui Song; Yanping Wang; Mingyu Zhang; Hamid Gholami; Shugang Kang; Yue Li; Shukhrat Shukurov; Nosir Shukurov; Rustam Orozbaev (Gondwana Research, 2025)

DNA damage repair (DDR) related prognostic risk model in multiple myeloma based on single-cell and bulk sequencing - Hongxiu Liu; Zhihua Li; Yihua Wang; Can Li; Kaiqing Yan; Yanping Ma (DNA Repair, 2025)

Melatonin Ameliorates Senescence of Mouse Auditory Cell Line HEI-OC1 Cells by Suppressing NLRP3 Inflammasome-Mediated Pyroptosis - Yongqing Ding; Yachao Liu; Dong Li; Ruili Hu; Zedong Tian; Lihang Yang; Yanping Li; Yantao Lin; Yan Qu (Molecular Neurobiology, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

The poleward expansion of the Hadley Cell has weakened the winter circulation in a midlatitude semi-enclosed shelf sea over the past six decades - Fangguo Zhai; Hao Li; Yanping Ma; Yucheng Wang; Yujie Dong; Zizhou Liu; Yanzhen Gu; Peiliang Li (Climate Dynamics, 2025)

Persistent Wnt signaling affects IVF embryo implantation and offspring metabolism - Yanping Jia; Yingdong Liu; Yanhe Li; Xiaohong Guan; Junting Xu; Zihui Yan; Kuisheng Liu; Yalin Zhang; Dandan Bai; Jiani Xiang; Yan Zhang; Shangyu Hou; et al. (Science Bulletin, 2025)

Dust supply to the West Philippine Sea since the Middle Pleistocene and distinct influences of the Westerlies after the Mid-Brunhes Event - Yun Cai; Dong Xu; Haifeng Wang; Yanping Chen; Haiyan Jin; Yibing Li; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Rewiring the methanol assimilation pathway in the methylotrophic yeast Pichia pastoris for high-level production of erythritol - Shuxian Wang; Jiayu Fang; Meiyu Wang; Sijie Yu; Yan Xia; Guoxia Liu; Yanping Zhang; Yin Li; Taicheng Zhu (Bioresource Technology, 2025)

Transcriptomics and Metabolomics Analysis Reveal the Mechanism of Hormones Regulation of the Flower Bud Formation and Development in Phalaenopsis Orchid - Xiaofen Gao; Yang Hao; Xiaoying Yang; Yanping Shi; Li Zhang; Rui Yan (Journal of Plant Growth Regulation, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

Enhancing the quality of dark tea through fermentation with Aspergillus niger: Unveiling aroma and taste characteristics - Maoyun Li; Sicheng Du; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Renyou Gan; Hong Gao (Food Microbiology, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Fabrication of biodegradable mulch film based on polylactic acid waste liquid - Dongfang Wang; Zerong Song; Xianghai Kong; Jie Wu; Jinjing Xu; Jinghong Ye; Yanping Zhu; Rongjun Zhang; Xiaoli Ma; Gang Li; Shifang Xu; Dongqing Cai (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Trait segregation and growth characteristics of the F2 generation hybrids between Crassostrea dianbaiensis and C. iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture International, 2025)

Comparison of genetic diversity and population structure of Saccostrea mordax lineages A, B, and C across South China Sea and Celebes Sea - Yinjie Zhang; Haitao Ma; Chenghui Han; Zhen Zhao; Zonglu Wei; Xixi Duan; Jiangwei Li; Yanping Qin; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Frontiers in Marine Science, 2025)
Saccostrea mordax is an ecologically important bivalve species and a potential genetic resource for oyster breeding that inhabit in the Indo-Western Pacific region, characterized by three distinct lineages: A, B, and C. However, limited information is available about its genetic variation and genetic structure. The present study was conducted to study genetic diversity and population structure of S. mordax lineages A, B, and C based on mitochondrial COI gene data across the South China Sea and Celebes Sea. The UPGMA phylogenetic tree among populations, BI phylogenetic tree among individuals and median network revealed three main clusters, corresponding to S. mordax lineages A, B, and C. The results of K2P sequence divergence, pairwise Φ st, gene flow and AMOVA indicated clear genetic differences among the lineages, combined with sympatric in all 7 geographical populations, these suggests lineages A and B are transitional periods of new species formation. Moreover, different patterns of population subdivision were found within lineages A, B and C. In lineage A, significant genetic differentiation was only observed between YM (Celebes Sea) and other populations (South China Sea), with a significant correlation between geographical distance and genetic distance among populations. In lineages B and C, there was no genetic differentiation between YM (Celebes Sea) and other populations (South China Sea), and no significant correlation between genetic distance and geographical distance among populations. The population history analyses indicated that populations of lineage A have experienced a recent sudden expansion, while populations of lineages B and C were large stable. These findings are essential for the conservation, sustainable utilization, and ecological restoration of S. mordax .

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Effects of trigonelline, diosgenin, and Cistanche deserticola polysaccharide on the culture of female germline stem cells in vitro - Xiaoli Yu; Yikai Qiu; Jinhua Li; Yanping Zhang; Qian Wang; Zehua Jin; Xinrui Liu; Xiuying Pei (Natural Product Research, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Unveiling insecticidal compounds from the invasive weed Tithonia diversifolia against Spodoptera litura and elucidating mechanisms via transcriptomic analysis - Zhandi Wang; Xiaocui Zhuang; Kaixiang Chao; Yanping Li; Lin Jia; Caiyun Zi; Yuanqing Zhou (Pesticide Biochemistry and Physiology, 2025)

2,4,6-trinitrotoluene induces neurotoxicity by affecting the G protein pathways in Caenorhabditis elegans - Ying Li; Yanping Zhou; Chunyan Wang; Yaguang Nie; Yongbing Zhu; Sanping Zhao; Lijun Wu; An Xu (NeuroToxicology, 2025)

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Multi-objective decision-making considering future demands helps to delineate key areas for ecological restoration in Changsha-Zhuzhou-Xiangtan urban agglomeration, China - Tao Li; Sheng Li; Yanping Zhao; Hua Zheng; Kuan Wang; Mi Yi (Journal of Environmental Management, 2025)

Selective adsorption of Rb+ and Cs+ by a superparamagnetic Fe₃O₄@FeMn-MOF from brine - Yanping Wang; Qiongyuan Zhang; Dezhen Fang; Kexin Li; Zhongmei Song; Wenjie Han; Junwei Li; Xiushen Ye; Haining Liu; Huifang Zhang; Xi Zhang; Zhijian Wu (Desalination, 2025)

Extracellular metabolites relieve the inhibitory effect of ferrous ions on microbial reduction of schwertmannite - Changdong Ke; Qian Yao; Yanping Deng; Siyu Zhang; Zhiliang Li; Renren Wu; Chuling Guo; Zhi Dang (Chemical Geology, 2025)

Paracoccus yibinensis sp. nov., a novel bacterium with astaxanthin producing isolated from the environment of Chinese distilled Baijiu - Qingchun Luo; Yanping Lu; Xi Li; Jian Su; Pengju Zhao; Zhu Zhang; Yang Gu; Dong Zhao; Jia Zheng (Antonie van Leeuwenhoek, 2025)

Influencing Factors on Oyster Recruitment and Performance Evaluation for Oyster Reef Restoration in Tianjin Coastal Zones - Yuxuan Zhao; Chen Yang; Bo Zhang; Yanping Li; Jianbo Tu; Fuxin Niu; Wenliang Kong; Zhiyun Wang; Xianhua Liu (Oceans, 2025)
Global oyster reefs have suffered severe degradation due to human activities, environmental pollution, and climate change. The construction of artificial reefs offers a promising strategy to enhance oyster recruitment and mitigate population decline. However, the factors influencing oyster recruitment in artificial frameworks remain largely unclear, and it is still challenging to evaluate the effectiveness of different restoration methods. In this study, a series of oyster reef restoration experiments were conducted in the Tianjin coastal zone to identify key factors affecting recruitment success. These factors included restoration methods (shell string, mesh bag, and mesh cage), seeding with juvenile oysters, oyster shell orientation, and cultch hanging height. Our results indicated that the mesh bag method achieved the highest oyster settlement density in the intertidal zone, while the shell string method supported the fastest growth rates of oysters in the subtidal zone. The lower hanging height of cultches in the artificial frames increased oyster settlement density; however, hanging the cultches too close to the sediment negatively impacted oyster growth rates. Additionally, seeding with juvenile oysters and orienting the rough side of the shell upward enhanced recruitment performance. Oyster settlement density was greater in the intertidal zone (Bagua Shoal) compared to the subtidal zone (Dashentang), while oysters in the subtidal zone exhibited faster growth rates. Using redundancy analysis, the influence of environmental factors on the oyster recruitment performance was assessed. Oyster growth in the subtidal zone was positively correlated with dissolved oxygen and pH, whereas oyster settlement density in the intertidal zone was positively associated with water temperature, chlorophyll a concentration, and salinity. Finally, we evaluated the effectiveness of different restoration methods by considering factors including reef construction costs, oyster settlement abundance, average daily shell growth rate, water purification potential, and reef subsidence. Our results demonstrated that the shell string method was the most effective in the Dashentang subtidal zone, while the mesh bag method with oyster seeding was optimal in the Bagua Shoal intertidal zone. Our findings can provide valuable insights and guidance for oyster reef restoration projects.

Offspring performance of backcrossing between hybrid line of Crassostrea dianbaiensis ♀ × Crassostrea iredalei ♂ and their parental species - Jiangwei Li; Yanping Qin; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Understanding nitrate dynamics in urbanized and forested river ecosystems: A study integrating natural-abundance and paired isotopes - Jian Zhang; Hao Jiang; Wentao Li; Yanping Li; Wenshi Zhang; Ke Pan (Journal of Environmental Management, 2025)

Chemical fractionation and isotopic analysis of lead in sediments from the Taipu River, integrated demonstration zone in the Yangtze River Delta, China - Yaojen Tu; Pengcheng Luo; Meichuan Chien; Yanping Duan; Jiayi Kou; Shenghui Liu; Yalong Li (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Templating effect of monoglycerides in controlling the spatial distribution of solid fat crystals within double emulsions - Yanping Huang; Zengliu Song; Yang You; Yunqi Li; Tongfei Shi; Jie Xiao (Food Chemistry, 2025)

Study of the interaction between polysaccharides and liposomes based on low-field nuclear magnetic resonance - Tingting Zhang; Heng Yu; Chenping Li; Yanping Wang; Chenxi Zheng; Yingli Hu; Jianzhong Han; Jianhua Liu; Weilin Liu (Food Bioscience, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Growth performance of two brackish oysters (Crassostrea iredalei and Crassostrea dianbaiensis) and their hybrids in subtropical sea area - Jiangwei Li; Ying Pan; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Shengyong Li; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture, 2025)

Chinese chestnut did not induce negative plant soil feedback during centuries of growth - Xu Cheng; Zhichun Yan; Qian Li; Lucas Schmitz; Jundi Yan; Yueyang Ge; Yanping Lan; Yaceng Zhao; Yiyang Wang; Guangdong Li; Yang Liu; Martinus Schneijderberg; et al. (Science of The Total Environment, 2025)

Automated calibration of Noah-MP land surface model for improved irrigation representation in the North China Plain - Danqiong Dai; Yanping Li; Liang Chen; Fei Chen; Zhenhua Li; Zhe Zhang; Prasanth Valayamkunnath; Li Xu; Cenlin He; Zhuguo Ma (Journal of Hydrology, 2025)

An intelligent biomass aerogel label loaded with anthocyanin from wasted peanut seed coat for monitoring chilled chicken freshness - Ling Li; Chaomei Zhou; Yongju Xu; Xu Zheng; Yanping Wu; Bin Yan; Kai Zhong; Hong Gao (Food Hydrocolloids, 2025)

Self-healing physiological monitoring epidermal sensors of dual conductivity pathway with self-adaptive transformation - Liao Ziming; Zhu Ximing; Zhang Shuquan; Liu Tingting; Song Jiamei; Wang Yuhong; Guo Yanping; Li Xiaohong; Ji Xiaoyuan; Yao Bin (Chemical Engineering Journal, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

Aquaporin ZmPIP2;4 promotes tolerance to drought during arbuscular mycorrhizal fungi symbiosis - Ying Ni; Hui Bao; Ruifan Zou; Yanping Wang; Kailing Xie; Beijiu Cheng; Xiaoyu Li (Plant and Soil, 2025)

Monosome Stalls the Translation Process Mediated by IGF2BP in Arcuate Nucleus for Puberty Onset Delay - Yifen Shen; Le Zhang; Tao Yang; Xiaosong Li; Chao Liu; Hongmei Li; Yanping Hu; Hao Shen; Hua Li; Yuriy L. Orlov; Shasha Zhou; Yihang Shen (Molecular Neurobiology, 2025)

Research on the impact of the belt and road initiative on the carbon emission performance of countries along the route - Jing Li; Yanping Zhou; Huiying Chen (Environment, Development and Sustainability, 2025)

Suyin Detoxification Prescription Regulates the Klotho and ERK/NF-κB Signaling Pathways to Alleviate Renal Injury - Lianghui Shu; Li Quan; Yanping Wang; Yanlin Chen; Chen Yong; Fang Tian; Kun Gao; Enchao Zhou (Cell Biochemistry and Biophysics, 2025)

Three-dimensional changes in temperature and circulation caused by northwestward-moving typhoons in a temperate semi-enclosed shelf sea in summer - Yanping Ma; Fangguo Zhai; Xingchuan Liu; Cong Liu; Zizhou Liu; Yanzhen Gu; Peiliang Li (Frontiers in Marine Science, 2025)
Due to the complex coastline and topography, changes of temperature and circulation in global shelf seas caused by typhoons have significantly region-specific three-dimensional structures. As one temperate semi-enclosed shelf sea, the Yellow Sea is highly susceptible to typhoons in summer. In August 2012 Typhoon Damrey moving northwestward over the Yellow Sea was observed to cause significant bottom temperature warming in the southern coastal waters of the Shandong Peninsula, but its impacts on the three-dimensional changes of temperature and circulation in the whole Yellow Sea and the underlying dynamics are still unclear. Using observations and high-resolution numerical simulations, we showed that during Damrey’s passage the South Yellow Sea exhibited spatially coherent surface cooling, particularly forming a distinct surface cooling band on the right side of the typhoon track. With the mixed layer deepening, the subsurface layer deepened and experienced temperature warming, especially on the right side of the typhoon track. The surface cooling and subsurface warming were primarily caused by strong wind-enhanced vertical mixing. In the deep layer, temperature exhibited pronounced warming in the southern coastal waters of the Shandong Peninsula but cooling in a southeast-northwest band along the bottom slope just off the Subei Shoal. Bottom temperature warming in the southern coastal waters of the Shandong Peninsula was caused by coastal downwelling resulting from upper layer coastward Ekman transport. Conversely, vertically consistent temperature cooling just off the Subei Shoal was caused by coastward and upward advection of cold water across the temperature fronts and thermocline due to surface layer Ekman divergence. The intensity and spatial distributions of temperature cooling just off the Subei Shoal were related to the distance between the typhoon track and Subei Shoal. Closer proximity of the typhoon track to the Subei Shoal would lead to more pronounced bottom cooling. This study enriches our understanding of three-dimensional hydrodynamic changes induced by typhoons with different tracks in the Yellow Sea.

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Neurotoxicity study of cenobamate-induced zebrafish early developmental stages - Jiahao Liu; Liya Fang; Chao Gong; Jiawei Li; Yuanyuan Liu; Pei Zeng; Yanping Fan; Yao Liu; Jin Guo; Luchuan Wang; Yue Li (Toxicology and Applied Pharmacology, 2025)

Enhanced fermentation of radish paocai with Lactiplantibacillus plantarum CBPC and shelf-life extension using e-beam irradiation - Ling Li; Qian Zhou; Zimeng Zheng; Luzhou Cai; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2025)

The importance of organic matter in controlling the metal variability and mobility in seagrass sediments - Shanshan Chen; Shiquan Chen; Zhenghua Tao; Yanping Li; Paolo Magni; Li Zhang; Xinqing Zheng; Ke Pan (Environmental Pollution, 2025)

New insights into interfacial dynamics and mechanisms of biochar–derived dissolved organic matter on arsenic redistribution in Schwertmannite - Xiaofei Li; Tianfu Li; Yanfu Wei; Xiaohu Jin; Suresh C. Pillai; Jun Zhang; Dian Chen; Xiaolian Wu; Yanping Bao; Xueding Jiang; Hailong Wang (Environmental Pollution, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Fluorinated Zn-porphyrin covalent organic frameworks with optimized hydrophobic/hydrophilic balance towards stable Zn anodes - Xia Li; Yanping Chu; Shouliang Lu; Liangdan Chen; Long Su; Fei Lu; Zhen Chen; Xinpei Gao (Chemical Engineering Journal, 2025)

Corrigendum to “Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei” [Aquaculture, Volume 595, Part 2, 30 January 2025, 741656] - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

Facile fabrication of porous fluorinated polyurethane membranes for organic solvent adsorption based on thiol-ene click reaction within high internal phase emulsions - Aili Wang; Yuyang Liu; Yanping Yu; Minxin Song; Jinyue Li; Yutong Wang; Caiyang Zhang; Nan Lou; Fang Qi; Xueyi Han (Process Safety and Environmental Protection, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

A portable microfluidic platform for ultra-sensitive detection of ovarian cancer biomarkers via cascade signal amplification - Yuzhen Wang; Wenxiu Long; Yanping Wang; Yuanyue Han; Fei Zeng; Jingjing Li; Bangshun He; Yujun Song; Yanfeng Gao (Chemical Engineering Journal, 2025)

Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping Qu; Hongcui Li; Ibrahim Yakub; Wen He; Wenchan Dong; Mohamad Hardyman Barawi; Sirui Wang; Huimin Ma; Zhenpeng Zhu (Water, Air, & Soil Pollution, 2025)

Integrating network pharmacology and experimental verification to explore the pharmacological mechanisms of phlorizin against osteoarthritis - Yi Yao; Qiuling Zhong; Yanping Zhong; Zixin Gao; Bo Zhou; Chun Lu; Li Zheng; Feiying Yin; Manli Tan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Mandarin Fish Ranavirus ( MRV ) Infection Induced Inflammation and Histologic Lesions in the Gut of Mandarin Fish - Xinru Gao; Ziye Zhang; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Journal of Fish Diseases, 2025)
Mandarin fish ranavirus (MRV) is widely spread in China and causes huge economic losses to the mandarin fish ( Siniperca chuatsi ) aquaculture. However, the pathogenesis of MRV is still unclear. In the present study, mandarin fish were artificially infected with MRV, and then different gut compartments from diseased fish were subjected to histologic analysis by H&E staining, quantification of proinflammatory genes and MRV copies by qPCR. MRV‐MCP protein expression was assessed using indirect fluorescence assay (IFA) and immunohistochemistry. Proliferation of IgM + B cells was evaluated by indirect fluorescence assay (IFA). Then, we found that MRV infection caused serious histologic lesions along with inflammatory cell infiltration, especially in the foregut. A significant accumulation of IgM + B cells was detected in the foregut (~6.5‐fold) and hindgut (~3.3‐fold), respectively. The expression of inflammation‐related genes such as IL‐1β, IL‐6, IL‐8, TNF‐α, CSF1r and NCF1 was significantly upregulated in the foregut, varying from ~2.8‐fold to ~11.9‐fold. In addition, MRV exhibited foregut tropism, according to the investigation of viral loads and MCP protein expression. Overall, our findings indicated that MRV‐induced hyperinflammation in the gut eventually led to enteritis. This study provided new insights into uncovering the pathogenesis of MRV infection.

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Unveiling the impact of exposed mineral facets on chromium repartitioning in aging lepidocrocite - Xiaofei Li; Chuling Guo; Xiaohu Jin; Qian Yao; Yanping Bao; Xueding Jiang; Guining Lu; Suresh C. Pillai; Hailong Wang; Zhi Dang (Science of The Total Environment, 2024)

Climate change drives fish communities: Changing multiple facets of fish biodiversity in the Northwest Pacific Ocean - Shuhao Liu; Yang Liu; Qinwang Xing; Yuru Li; Hao Tian; Yanping Luo; Shin-ichi Ito; Yongjun Tian (Science of The Total Environment, 2024)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

Ecologically friendly remediation of groundwater sulfamethoxazole contamination: Biologically synergistic degradation by thermally modified activated carbon-activated peracetic acid in porous media - Si Li; Ruizhe Xu; Luochao Wan; Chaomeng Dai; Jixiang Li; Xueji You; Yanping Duan; Xiaoying Lai; Zhi Li; Jifeng Guo; Yalei Zhang; Jiajun Hu; et al. (Journal of Hazardous Materials, 2024)

Estimation and attribution of nonlinear trend of water use efficiency using a normalized partial derivative approach - Shahid Naeem; Yongqiang Zhang; Congcong Li; Yanping Li; Tahir Azeem; Rashid Mahmood (Journal of Environmental Management, 2024)

An evaluation method for synergistic effect of air pollutants and CO2 emission reduction in the Chinese petroleum refining technology - Dandan Liu; Xueying Li; Dong Wang; Hao Wu; Yanping Li; Yanjun Li; Qi Qiao; Zhou Yin (Journal of Environmental Management, 2024)

Novel advanced oxidation technology of Fe2+-activated peracetic acid for high efficient disintegration of waste activated sludge - Wenqi Liu; Yanping Zhang; Jing Zhang; Ning Lv; Yibing Li (Journal of Environmental Chemical Engineering, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

A study on the structure-functionality relationship of Solenaia oleivora protein under high-intensity ultrasonication processing - Wanwen Chen; Wu Jin; Xueyan Ma; Haibo Wen; Yanping Li; Gangchun Xu; Pao Xu; Hao Cheng (Food Chemistry, 2024)

Effects of valley topography on ozone pollution in the Lanzhou valley: A numerical case study - Wenkai Guo; Yanping Yang; Junke Zhang; Keran Han; Yinhua Yang; Qiang Chen; Shixue Li; Yuhuan Zhu (Environmental Pollution, 2024)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

A 3D self-floating evaporator loaded with phase change energy storage materials for all-weather desalination - Yuqin Teng; Shuai Li; Yanxia Luo; Xin Yi; Libang Feng; Dianming Li; Yanping Wang (Desalination, 2024)

Construction of a redox-coupled pathway co-metabolizing glucose and acetate for high-yield production of butyl butyrate in Escherichia coli - Tianrui Zhang; Guoxia Liu; Yin Li; Yanping Zhang (Bioresource Technology, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Experimental investigation on strength characteristics of marine soft clay under monotonic and cyclic loading - Lin Guo; Hao Wu; Yanping He; Hui Li; Yilong Sun (Marine Georesources & Geotechnology, 2024)

Enhanced 3D dose prediction for hypofractionated SRS (gamma knife radiosurgery) in brain tumor using cascaded-deep-supervised convolutional neural network - Nan Li; Jinyuan Wang; Yanping Wang; Chunfeng Fang; Yaoying Liu; Chunsu Zhang; Dongxue Zhou; Lin Cao; Gaolong Zhang; Shouping Xu (Physical and Engineering Sciences in Medicine, 2024)

Salidroside Reduced Ca2+-CaM-CAMKII-Dependent eNOS/NO Activation to Decrease Endothelial Cell Injury Induced by Cold Combined with Hypoxia - Hongjin Wang; Xianzhen Wang; Yanping Feng; Kewei Zhang; Maodongzhi Peng; Xiaowei Wu; Yi Li (Cell Biochemistry and Biophysics, 2024)

Numerical investigation on effects of fuel rod with the position of bow deformation on the flow and heat transfer of PWR - Chengde Li; Mei Huang; Delong Sun; Xiaoping Ouyang; Yanping Huang; Yang Liu (Annals of Nuclear Energy, 2024)

Evaluating AGS efficiency in PHA synthesis and extraction integrated with nutrient removal: The impact of COD concentrations - Quan Yuan; Song Chen; Yun Chen; Xinyu Zhang; Yuqing Lou; Xueting Li; Qian Liang; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Microplastics distribution, ecological risk and outflows of rivers in the Bohai Rim region of China - A flux model considering small and medium-sized rivers - Xin Hou; Jiayao Li; Hongyu Li; Shuyun Du; Sitong Liu; Shipu Jiao; Fuxin Niu; Jianbo Tu; Yanping Zong; Xiaotong Wang; Xianhua Liu (Science of The Total Environment, 2024)

Numerical simulation and deep-sea experiment validation for the cathodic protection design of aluminum alloy framework - Tigang Duan; Yu Zhang; Li Ma; Shaohua Xing; Yanping Liu; Wenshan Peng; Haibing Zhang; Jian Hou (Ocean Engineering, 2024)

Impact of geochemistry and microbes on the methylmercury production in mangrove sediments - Jingli Liu; Yanping Li; Aijia Zhang; Huan Zhong; Hao Jiang; Martin Tsz-Ki Tsui; Meng Li; Ke Pan (Journal of Hazardous Materials, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

Multi-drug loaded electrospinning nanofibers promote healing with less scar formation by remodeling wound microenvironment via modulating TGF-β1/Smads/EN1 signal - Xiaoyan Zeng; Zhenfeng Guan; Reyisha Yusufu; Siyi Li; Qi WU; Yanping Feng; Tiantian Chen; Muxiang Luo; Fenghuan Wei (Chemical Engineering Journal, 2024)

Corrigendum to “Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding” [Aquaculture 563 (2023) 738910] - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Successive selection responses of tetraploid Crassostrea angulata: Comparison of growth, survival, sex ratio and ploidy composition between selected and unselected groups - Yanping Qin; Weitao Wan; Jiangwei Li; Chao Yue; Zhongyu Wang; Qinggan Xing; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Two-stage hydrothermal liquefaction of Spirulina: Experimental observations, energy analysis and techno-economic assessment - Hongwei Pang; Yanping Feng; Xinru Ma; Qirong Yang; Zhaoying Li (Process Safety and Environmental Protection, 2024)

Facile in-situ fabrication of graphene oxide/poly(ionic liquid) composites and their adsorption performance for methyl orange - Xiaoying Wang; Yuyang Liu; Xiuzhi Liu; Caiyang Zhang; Minxin Song; Yanping Yu; Xueyi Han; Jinyue Li; Aili Wang (Process Safety and Environmental Protection, 2024)

Source apportionment of organic carbon and nitrogen in sediments from river and lake in the highly urbanized Changjiang Delta - Yalong Li; Yaojen Tu; Tingting Sun; Yanping Duan; Jiayi Kou; Weikun Li; Jiaxin Gao (Journal of Hazardous Materials, 2024)

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Virtual screening reveals fluorescent probes for detecting Pan-Zinc center activity in serum MMPs: A potential biomarker for early tumor screening - Shang Ju; Yi Xiang; Yajun Xie; Lei Zuo; Juqiong Li; Xiaorong Li; Yanping Wang; Qin Huang; Min Zhang; Xiaomian Wu; Yuanyuan Wang; Qiong Shi; et al. (Chemical Engineering Journal, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Adsorption mechanism and remediation of heavy metals from soil amended with hyperthermophilic composting products: Exploration of waste utilization - Feng Ma; Tong Zhu; Youzhao Wang; Shuichi Torii; Zhipeng Wang; Chaoyue Zhao; Xu Li; Yanping Zhang; Haoyu Quan; Chunli Yuan; Liying Hao (Bioresource Technology, 2024)

DGA ameliorates severe acute pancreatitis through modulating macrophage pyroptosis - Xiyue Yue; Lunmeng Lai; Ruina Wang; Lulu Tan; Yanping Wang; Qing Xie; Yunsen Li (Inflammation Research, 2024)

Ginsenoside Rg1 treats chronic heart failure by downregulating ERK1/2 protein phosphorylation - Liqi Peng; Shaodong Li; Huzhi Cai; Xueliang Chen; Yanping Tang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Disruption of BACH1 Protects AC16 Cardiomyocytes Against Hypoxia/Reoxygenation-Evoked Injury by Diminishing CDKN3 Transcription - Yanping Li; Yi Zhou; Haifeng Pei; De Li (Cardiovascular Toxicology, 2024)

Screening of promising molecules against potential drug targets in Yersinia pestis by integrative pan and subtractive genomics, docking and simulation approach - Lei Chen; Lihu Zhang; Yanping Li; Liang Qiao; Suresh Kumar (Archives of Microbiology, 2024)

The practice and innovation of compatible marine utilization models in China - Yanping Li; Yan Yang; Yuting Hou; Xiao Liu; Dahai Liu (Frontiers in Marine Science, 2024)
Marine Spatial Planning (MSP) is essential for optimizing marine resources allocation and resolving conflicts in sea use, but it is challenged by the complex and multi-functional nature of maritime resources. This study utilizes participatory methods, inductive reasoning, and overlay analysis to explore both theoretical and practical aspects of compatible marine utilization models. The paper begins by clarifying the logic of compatible sea use through marine functional zoning and identifying its core characteristics: quantity, spatial conflict, and impacts on natural attributes. Building on China’s national territorial spatial planning reforms and practical experiences, the paper introduces three major categories of compatible marine use models: development sequencing compatibility, spatial coexistence compatibility, and functional synergy compatibility. A compatibility discrimination matrix is developed to assess these models across different marine functional areas. Combined with the compatibility discrimination results, taking the marine and coastal spatial planning of Yantai City in China as a case study, the paper analyzes the compatibility demands and planning strategies within various marine functional areas. Finally, it evaluates the risks associated with each compatibility model and proposes targeted control strategies tailored to the specific features of each model and characteristics of sea use activities. The research findings highlight the positive role of compatible sea use models in promoting marine economic development, enhancing spatial efficiency, and mitigating sea use conflicts. However, these models also present varying potential risks, necessitating differentiated control strategies aligned with legal frameworks and specific sea use activities. The study offers valuable insights for MSP and contributes to the efficient utilization of marine resources and the advancement of marine spatial governance.

Design of Auto-Adaptive Drug Delivery System for Effective Delivery of Peptide Drugs to Overcoming Mucus and Epithelial Barriers - Ruihuan Ding; Yanping Li; Wei Zheng; Yiying Sun; Zhenyu Zhao; Houqian Zhang; Ranran Yuan; Aiping Wang; Kaoxiang Sun; Hongbo Wang; Yanan Shi (The AAPS Journal, 2024)

Effect of long-term dosage of hydrazine on mainstream anammox process: Biofilm characteristics and microbial community - Quan Yuan; Yuqing Lou; Song Chen; Yun Chen; Xueting Li; Xinyu Zhang; Liang Qian; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Exploring potential causal links between air pollutants and congenital malformations: A two-sample Mendelian Randomization study - Shufen Li; Yanping Zhang; Kaiyan Yang; Wenbo Zhou (Reproductive Toxicology, 2024)

Design and numerical simulation of the elastomeric support for the topside modules of an FPSO - Yucu Huang; Yanping He; Yadong Liu; Ming Qiu; Mingzhi Li (Ocean Engineering, 2024)

Effect of biochar-derived DOM on contrasting redistribution of chromate during Schwertmannite dissolution and recrystallization - Xiaofei Li; Tianfu Li; Paramsothy Jeyakumar; Jiayi Li; Yanping Bao; Xiaohu Jin; Jun Zhang; Chuling Guo; Xueding Jiang; Guining Lu; Zhi Dang; Hailong Wang (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

Electrochemistry promotion of Fe(Ⅲ)/Fe(Ⅱ) cycle for continuous activation of PAA for sludge disintegration: Performance and mechanism - Jing Zhang; Yanping Zhang; Ning Lv; Fen Li; Yibing Li; Zhenjie Guo (Environmental Research, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

A numerical method for two-dimensional transient nonlinear convection-diffusion equations - Xiangyuan Meng; Mei Huang; Boxue Wang; Xiaoping Ouyang; Yanping Huang; Denggao Chen; Yanting Cheng; Yaodi Li (Annals of Nuclear Energy, 2024)

An explainable integrated machine learning model for mapping soil erosion by wind and water in a catchment with three desiccated lakes - Hamid Gholami; Mehdi Jalali; Marzieh Rezaei; Aliakbar Mohamadifar; Yougui Song; Yue Li; Yanping Wang; Baicheng Niu; Ebrahim Omidvar; Dimitris G. Kaskaoutis (Aeolian Research, 2024)

A global assessment of nested patterns in insular mammal assemblages - Virginie Millien; Chengxiu Zhan; Yanxia Li; Jiang Wang; Yanping Wang (Global Ecology and Biogeography, 2024)
Aim A nested pattern (nestedness) in species composition is a frequent signature of insular communities. However, it remains unclear whether the drivers of nestedness are consistent across multiple island systems. Here, we investigated the pattern and drivers of taxonomic, functional and phylogenetic nestedness in terrestrial mammal assemblages from 10 distinct island systems (archipelagos). Location Global. Time period Contemporary. Major taxa studied Terrestrial mammals. Methods We compiled occurrence data and species traits of terrestrial mammals from 228 islands in 10 distinct island assemblages. We assembled a dataset of island biogeographic characteristics for each of these islands, including island area, isolation index and maximum elevation. For all 10 assemblages, we first tested for significant patterns of taxonomic, functional and phylogenetic nestedness. We then examined the associations between nestedness, island biogeographic characteristics and species traits. Results We detected significant patterns of taxonomic, functional or phylogenetic nestedness in mammal assemblages from all 10 archipelagos. Biogeographic characteristics of islands affecting the rate of extinction in island species, namely, island area and elevation, were significantly associated with the degree of nestedness in these assemblages. Traits associated with the extinction probability of a species, such as litter size, further drove the nested pattern in some assemblages. Main conclusions All analyses pointed to selective extinction as a main mechanism shaping the observed nested patterns in island mammal assemblages. From a conservation point of view, different management strategies should be implemented for mammal assemblages in these island systems by identifying the drivers of species extinction rates specific to each island system and species occurring on these islands.

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

Spatial heterogeneity and driving mechanisms of carbon storage in the urban agglomeration within complex terrain: Multi-scale analyses under localized SSP-RCP narratives - Hongyi Zhang; Xin Li; Yanping Luo; Lu Chen; Minxi Wang (Sustainable Cities and Society, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Condition-based maintenance method for multi-component systems under discrete-state condition: Subsea production system as a case - Rongkang Li; Baoping Cai; Yixin Zhao; Yiliu Liu; Yanping Zhang; Xiangdi Kong; Yonghong Liu (Ocean Engineering, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Comparison of anaerobic co-digestion of vacuum toilet blackwater and kitchen waste under mesophilic and thermophilic conditions: Reactor performance, microbial response and metabolic pathway - Ziang Wang; Haixiang Li; Pingbo Wang; Jia Zhu; Ziyi Yang; Yanping Liu (Journal of Environmental Management, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Leaf morpho-anatomy and taxonomic significance in five Dendrobium sect. Stachyobium species from China - Yunxi Xie; Yanping Wang; Lei Tao; Wenhao Liu; Yan Luo; Lu Li (Flora, 2024)

Effect of Sulfate and Acid Orange 7 on Sb(V) Removal by Anaerobic Granular Sludge: Role of Granular Activated Carbon - Qi Li; Yanping Zhu; Yanbiao Liu; Xiaoguang Chen; Nan Jiang; Mengying Yan; Xuhua Li; Haoyu Xing; Yinzhou Bao; Manhong Huang (Water, Air, & Soil Pollution, 2024)

An EEG-based marker of functional connectivity: detection of major depressive disorder - Ling Li; Xianshuo Wang; Jiahui Li; Yanping Zhao (Cognitive Neurodynamics, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Connotation analysis and path discussion of China’s land-sea coordination policy: based on the interregional externality theory - Yanping Li; Yuping Wang; Dahai Liu; Yuting Hou (Frontiers in Marine Science, 2024)
As two spatial geographic units that are both independent of each other and closely linked, the land and sea have complex spatial interactions. Therefore, China implements the land-sea coordination policy (LSC) needs to be approached from a more macroscopic, systematic and comprehensive perspective. Based on the interregional externality theory, this study takes the land-sea coordination policy of China as an example, and focuses on the interaction process and manifestation between land and sea, and then explores the connotation and realization path of LSC. Firstly, we delineated the spatial unit and analyzed the land-sea interactions (LSI) using Vensim software. Secondly, the characteristics and manifestations of LSI are summarized from the perspective of interregional externalities. Finally, this study elucidates the foundational concept of implementing LSC and further propose actionable pathways for promoting land and sea development in a coordinated way, aimed at offering supportive decision-making insights for achieving LSC within the broader framework of China’s territorial spatial planning. Initiating LSC implementation involves strategies such as source control, process management, and interaction interface optimization. Deepening LSC effectiveness entails strengthening positive interregional externalities while mitigating negative interregional externalities.

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Novel insight into the formation and improvement mechanism of physical property in fermented tilapia sausage by cooperative fermentation of newly isolated lactic acid bacteria based on microbial contribution - Qiaoyan Cui; Laihao Li; Hui Huang; Yanping Yang; Shengjun Chen; Chunsheng Li (Food Research International, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Chiral dual-core emitters based-on through-space coupling for high-performance OLEDs with little efficiency roll-off - Lifen Chen; Mingjia Deng; Shao-Yun Yin; Yu Fu; Yingxiao Mu; Jia-Xiong Chen; Lingyun Cui; Shaomin Ji; Yanping Huo; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Identification and functional analysis of floral terpene synthase genes in Curcuma alismatifolia - Zihan Cao; Lan Wang; Di Huang; Guilan Wu; Xinyue Li; Yuechong Yue; Yunyi Yu; Rangcai Yu; Yanping Fan (Planta, 2024)

Involvement of a rice mutation in storage protein biogenesis in endosperm and its genomic location - Huaidong Tian; Ying Li; Yanping Guo; Yajuan Qu; Xiaoye Zhang; Xiaoxian Zhao; Xinya Chang; Baohua Tian; Guangyuan Wang; Xiangmei Yuan (Planta, 2024)

Evolution of runoff discharge patterns and risk assessment of water inrush in mountainous railroad tunnels - Xu Yang; Dandan You; Xin Gao; Qi Li; Xinhao Hu; Saixing Zeng; Jingxiao Zhang; Yanping Hu; Lanxin Kang (Natural Hazards, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

Interaction mechanism of global multiple ocean-atmosphere coupled modes and their impacts on South and East Asian Monsoon: A review - Guiping Li; Zhongbo Yu; Yanping Li; Chuanguo Yang; Huanghe Gu; Jingwen Zhang; Ya Huang (Global and Planetary Change, 2024)

Gold-copper-doped lanthanide luminescent metal-organic backbone induced self-enhanced molecularly imprinted ECL sensors for ultra-sensitive detection of chlorpyrifos - Yishan Fang; Yanping Li; Xufeng Zang; Yingxue Chen; Xinran Wang; Na Wang; Xiangying Meng; Bo Cui (Food Chemistry, 2024)

Recent advances in the authentication (geographical origins, varieties and aging time) of tangerine peel (Citri reticulatae pericarpium): A review - Yanxin Li; Wenhong Zhao; Min Qian; Zhiyi Wen; Weidong Bai; Xiaofang Zeng; Hong Wang; Yanping Xian; Hao Dong (Food Chemistry, 2024)

Effects of enhanced fermentation with Lactiplantibacillus plantarum WWPC on physicochemical characteristics and flavor profiles of radish paocai and dried-fermented radish - Zimeng Zheng; Qian Zhou; Dong Li; Yanping Wu; Kai Zhong; Hong Gao (Food Bioscience, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Correction to: Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

Changes in the characteristics of soil dissolved organic matter over time since inter-planting with white clover (Trifolium repens L.) in apple orchards on the Loess Plateau in China - Rongqin Zhang; Ming Li; Xiaodong Gao; Yumin Duan; Yaohui Cai; Huike Li; Xining Zhao; Yanping Wang (Plant and Soil, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Characterization of a membrane Fcγ receptor in largemouth bass (Micropterus saloumoides) and its response to bacterial challenge - Jingya Wang; Jing Wu; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Fish Physiology and Biochemistry, 2024)

A within-subject voxel-wise constant-block partial least squares correlation method to explore MRI-based brain structure–function relationship - Xiaoyu Zhao; Kewei Chen; Hailing Wang; Yufei Gao; Xiangmin Ji; Yanping Li (Cognitive Neurodynamics, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Growth, survival and reproductive traits of chemical induced and tetraploid-derived triploid Hong Kong oysters (Crassostrea hongkongensis) - Yanping Qin; Weitao Wan; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Single-cell and multi-omics analyses highlight cancer-associated fibroblasts-induced immune evasion and epithelial mesenchymal transition for smoking bladder cancer - Jiajin Wu; Fang Gao; Rui Meng; Huiqin Li; Zhenguang Mao; Yanping Xiao; Qiuyi Pu; Mulong Du; Zhengdong Zhang; Qiang Shao; Rui Zheng; Meilin Wang (Toxicology, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

Preparation and Characterization of Magnetic Walnut Shell Adsorbents - Yanping Li; Qingxue Yu; Yujie Chang; Yongfa Shi (Water, Air, & Soil Pollution, 2024)

The feeding strategies of the antarctic lanternfish electrona antarctica (pisces: myctophidae) in the amundsen and cosmonaut seas (southern ocean), assessed with a classification tree analysis - Mi Duan; Chi Zhang; Yanping Luo; Libao Gao; Guankui Liu; Chunlin Liu; Yongming Sun; Jianchao Li; Shuyang Ma; Wenchao Zhang; Yongjun Tian (Polar Biology, 2024)

Genome-wide identification of nitrate transporter 1/peptide transporter family (NPF) induced by arbuscular mycorrhiza in the maize genome - Qiang Xu; Yanping Wang; Wen Sun; Yuanhao Li; Yunjian Xu; Beijiu Cheng; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2024)

MicroRNA-126 (MiR-126): key roles in related diseases - Li Liao; Yan Tang; Yanping Zhou; Xianglin Meng; Bo Li; Xiaochun Zhang (Journal of Physiology and Biochemistry, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Understanding the variable metal concentrations in estuarine oysters Crassostrea hongkongensis: A biokinetic analysis - Shaomei Yang; Yanping Li; Fengyuan Chen; Shanshan Chen; Xin Luo; Wei Duan; Yongyan Liao; Hao Jiang; Ke Pan (Marine Environmental Research, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Phenotypic traits of reciprocal tetraploid hybrids derived from tetraploid Crassostrea gigas and tetraploid Crassostrea angulata - Chao Yue; Yanping Qin; Weitao Wan; Gongpengyang Shi; Shengyong Li; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Honeybee symbiont Bombella apis could restore larval-to-pupal transition disrupted by antibiotic treatment - Chen Xiaowen; Li Jiahao; Ding Zhaorun; Li Wenfeng; Han Richou; Chen Yanping; Xie Huichun; Zhang Yi (Journal of Insect Physiology, 2024)

Biochar co-pyrolyzed from peanut shells and maize straw improved soil biochemical properties, rice yield, and reduced cadmium mobilization and accumulation by rice: Biogeochemical investigations - Weijie Xu; Xiaocui Xie; Qi Li; Xing Yang; Jiajia Ren; Yanping Shi; Dan Liu; Sabry M. Shaheen; Jörg Rinklebe (Journal of Hazardous Materials, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Untangling the critical success factors of the latest compulsory waste sorting initiative in Shanghai: The role of accountability governance - Shenghao Xie; Yu Gong; Abraham Zhang; Yanping Liu; Changjun Li (Journal of Cleaner Production, 2024)

Effects of wastewater treatment plant effluent on microbial risks of pathogens and their antibiotic resistance in the receiving river - Zijian Xiao; Yuanyuan Qin; Li Han; Yifan Liu; Ziyi Wang; Yanping Huang; Yujing Ma; Yina Zou (Environmental Pollution, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Measurement, influencing factors and prediction on carbon emission performance of countries along the Belt and Road - Jing Li; Yanping Zhou; Huiying Chen (Clean Technologies and Environmental Policy, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Study of the wet-towing transportation of an FPSO with elastomeric-supporting topside modules - Yucu Huang; Yanping He; Ming Qiu; Yadong Liu; Mingzhi Li (Ocean Engineering, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Exogenous Epigallocatechin-3-Gallate Alleviates Pesticide Phytotoxicity and Reduces Pesticide Residues by Stimulating Antioxidant Defense and Detoxification Pathways in Melon - Yaxian Wu; Golam Jalal Ahammed; Zhengzhen Li; Yameng Wang; Qianying Wang; Mingya Fang; Yanping Zhang; Haihe Liu; Xin Li (Journal of Plant Growth Regulation, 2024)

Trihalomethane prediction model for water supply system based on machine learning and Log-linear regression - Hui Li; Yangyang Chu; Yanping Zhu; Xiaomeng Han; Shihu Shu (Environmental Geochemistry and Health, 2024)

Highly Sensitive Detection of PIK3CA Mutations by Looping-Out Probes-Based Melting Curve Analysis - Boheng Xu; Yanping Lan; Danjiao Luo; Yangsi Zheng; Runfang Ni; Guoqiang Su; Qiuying Huang; Qingge Li (Biochemical Genetics, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Miniaturized ascorbic acid assay platform based on point discharge atomic emission spectrometry coupling with gold filament enrichment - Yanping Wang; Yuemei Chen; Kejun Li; Jinrong Zhou; Xin Yuan; Mei Zhang; Ke Huang (Analytica Chimica Acta, 2024)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Impact of facemask debris on marine diatoms: Physiology, surface properties, sinking rate, and copepod ingestion - Fengyuan Chen; Zhen Zhang; Yanping Li; Hao Jiang; Yanfei Zhou; Hongbin Liu; Ke Pan; Jie Ma (Science of The Total Environment, 2023)

A facile two-step method to construct environmental-friendly Janus coconut wood membrane for oil/water separation - Wanfei Yu; Xue Hou; Yanping Zhang; Weimin Wan; Peng Gao; Zihao Yan; Jianbao Li; Xue Hou (Journal of Water Process Engineering, 2023)

Advancements in technology and innovation for sustainable agriculture: Understanding and mitigating greenhouse gas emissions from agricultural soils - Muhammad Qayyum; Yanping Zhang; Mansi Wang; Yuyuan Yu; Shijie Li; Wasim Ahmad; Saleh N. Maodaa; Shaban R.M. Sayed; Jiawei Gan (Journal of Environmental Management, 2023)

Gas-expanded pore MOF derived Sm/MnOx catalysts enable ultralow-temperature selective catalytic reduction of NOx - Shengchen Li; Dan Zhao; Shunli Shi; Fangyu Zhu; Yanping Yang; Shuhua Wang; Shunmin Ding; Chao Chen (Journal of Environmental Chemical Engineering, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Walnut green husk extract enhances the effect of chlorine dioxide on kernel quality and antioxidant properties of fresh-eating walnuts during their shelf life - Dongli Zhang; Niu Ye; Mingrui Li; Guoli Dai; Yanping Ma; Yifan Wang; Chaobin Liu; Huiling Ma (Food Chemistry, 2023)

Multi-omics analysis of oxidative stress and apoptosis in hepatopancreas cells induced by Polyascus gregaria parasitizing the Eriocheir sinensis - Shiwei Zhao; Qingbiao Hu; Hongbo Jiang; Yingying Zhao; Yanping Wang; Chengcheng Feng; Xiaodong Li (Fish & Shellfish Immunology, 2023)

RNA interference of NADPH-cytochrome P450 reductase increases the susceptibility of Aphis gossypii Glover to sulfoxaflor - Qiuling Tang; Xuchao Li; Yanping He; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Novel aloe emodin–hydroxyethyl piperazine hybrid dihydrochloride induces oral cancer CAL-27 cells apoptosis through ROS production, DNA damage and mitochondrial pathways - Xing Long; Peilin Yang; Lin Chen; Wen Zhong; Shaofeng Chen; Yanping Li; Shijie Lin; Wei Tian (Medicinal Chemistry Research, 2023)

Impact of climate change under the RCP8.5 emission scenario on multivariable agroclimatic indices in Western Canada from convection-permitting climate simulation - Richard Y.K. Agyeman; Fei Huo; Zhenhua Li; Yanping Li; Mohamed E. Elshamy; Yunsung Hwang (Anthropocene, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Controlled synthesis of CuS with different morphology and pollution control of Hg0 in non-ferrous smelting flue gas - Jin Zhao; Xueqian Wu; Yanping Ma; Wei Liu; Zhen Li; Songjian Zhao (Fuel, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Efficient degradation of tetrabromobisphenol A using peroxymonosulfate oxidation activated by a novel nano-CuFe2O4@coconut shell biochar catalyst - Xinxin Li; Xujing Li; Chuang Song; Xiaojin Yang; Yanping Liu; Jia Zhu (Environmental Pollution, 2023)

Study on thermal properties of bio-char prepared by photo-thermal pyrolysis - Dexin Huang; Yankui Wang; Gongxiang Song; Song Hu; Hanjian Li; Yanping Zhang; Yi Wang; Sheng Su; Saad A. El-Sayed; Jun Xiang (Biomass and Bioenergy, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Enhancing alkali-activated materials with low quality fly ash: A novel mixing approach for robust construction materials - Reza Mirmoghtadaei; Lin Shen; Yanping Li; Mo Li; Baomin Wang (Journal of Cleaner Production, 2023)

Effective degradation of tetracycline by Pd/AG/ITO electrode: Electrode preparation, characterization, kinetics, degradation mechanism and toxicity assessment - Chen Shao; Jian Zhang; Yuqing Liu; Yuting Jiang; Yanping Jia; Guomin Li; Zhong Sun (Journal of Environmental Chemical Engineering, 2023)

Adding the third component with similar building blocks to regulate the miscibility of active layer enables high efficient ternary solar cells - Shichu Peng; Jinxin Luo; Peng Li; Liangang Xiao; Chongqing Yang; Yaocheng Jin; Ruiying Lin; Yanping Huo; Yi Liu; Yonggang Min (Chemical Engineering Journal, 2023)

The built-in electric field and spin-pinning effect in BiVO4/Fe0.4Co0.6Se2/Co(Fe)OxHy for enhanced photoelectrochemical water oxidation - Ben Fan; Ling Ding; Zebin Yu; Ronghua Jiang; Yanping Hou; Shuang Li; Jianhua Chen (Chemical Engineering Journal, 2023)

Risk factors of vestibular migraine-related brain white matter lesions - Yu Shen; Defu Li; Qian Cao; Mengyao Hu; Zhou Hou; Lijun Xu; Yanping Li; Daojun Hong (Acta Neurologica Belgica, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

Barriers to compulsory waste sorting for a circular economy in China - Abraham Zhang; Shenghao Xie; Yu Gong; Changjun Li; Yanping Liu (Journal of Environmental Management, 2023)

Comprehensive transcripts analysis based on single-molecule real-time sequencing and Illumina sequencing provides insights into the mining of Toll-like receptor family in Schizothorax lissolabiatus - Qian Duan; Qi Luo; Qian Tang; Lei Deng; Renyi Zhang; Yanping Li (Fish & Shellfish Immunology, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Climatological features of future MCSs over the Canadian Prairies using convection-permitting climate models - Yunsung Hwang; Xiao Ma; Richard Y.K. Agyeman; Yanping Li (Atmospheric Research, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Multiple-Batch Digestion of Community Solid Waste with Recirculated Slurry as Inoculum: Performance and Microbial Community - Jingjing Tong; Chuang Song; Mei Song; Maomao Yuan; Dexun Zou; Xinxin Li; Xusheng Zheng; Yanping Liu (BioEnergy Research, 2023)

Kinetic and thermodynamic analysis on preparation of belite-calcium sulphoaluminate cement using electrolytic manganese residue and barium slag by TGA - Weilong He; Rui Li; Yanping Yang; Yu Zhang; Dengpan Nie (Environmental Science and Pollution Research, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Effects of nanoplastics on clam Ruditapes philippinarum at environmentally realistic concentrations: Toxicokinetics, toxicity, and gut microbiota - Yanfei Zhou; Chao Wu; Yanping Li; Hao Jiang; Aijun Miao; Yongyan Liao; Ke Pan (Journal of Hazardous Materials, 2023)

Comparison between discarded facemask and common plastic waste on microbial colonization and physiochemical properties during aging in seawater - Jie Ma; Fengyuan Chen; Ciara Chun Chen; Zhen Zhang; Zihan Zhong; Hao Jiang; Junbao Pu; Yanping Li; Ke Pan (Journal of Hazardous Materials, 2023)

A review of metal contamination in seagrasses with an emphasis on metal kinetics and detoxification - Yanping Li; Fengyuan Chen; Ruojing Zhou; Xinqing Zheng; Ke Pan; Guanglong Qiu; Zhongjie Wu; Shiquan Chen; Daoru Wang (Journal of Hazardous Materials, 2023)

Nanoplastics impacts on Thiobacillus denitrificans: Effects of size and dissolved organic matter - Yuancheng Li; Chuling Guo; Siyu Zhang; Changdong Ke; Yanping Deng; Zhi Dang (Environmental Pollution, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

High expression of HOXC6 predicts a poor prognosis and induces proliferation and inflammation in multiple myeloma cells - Zhihua Li; Yaru Wang; Xiaoxu Hou; Luyao Guo; Yanling Li; Yanping Ma; Yanping Ma (Genes & Genomics, 2023)

A novel high-stability bioelectrochemical sensor based on sol-gel immobilization of lactate dehydrogenase and AuNPs-rGO signal enhancement for serum pyruvate detection - Yanping Zhao; Xu Geng; Xiaoling Zhou; Li Xu; Shuai Li; Zhengqiang Li; Yi Guo; Chen Li (Analytica Chimica Acta, 2023)

Machine learning algorithm inversion experiment and pollution analysis of water quality parameters in urban small and medium-sized rivers based on UAV multispectral data - Yikai Hou; Anbing Zhang; Rulan Lv; Yanping Zhang; Jie Ma; Ting Li (Environmental Science and Pollution Research, 2023)

Kinetics and mechanisms of bacteria disinfection by performic acid in wastewater: In comparison with peracetic acid and sodium hypochlorite - Ning Ding; Ziwei Li; Lin Jiang; Hong Liu; Yanping Zhang; Yingxue Sun (Science of The Total Environment, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

A double-glazed solar air-phase change material collector for nocturnal heating: Model development and sensitivity analysis - Li Yang; Nan Zhang; Yanping Yuan; Fariborz Haghighat; Mohamed Dardir; Karthik Panchabikesan; Qinrong Sun (Energy and Buildings, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Changes in overwintering ground of small yellow croaker ( Larimichthys polyactis ) based on MaxEnt and GARP models: A case study of the southern Yellow Sea stock - Guodong Li; Ying Xiong; Xiaming Zhong; Dade Song; Zhongjie Kang; Dongjia Li; Jianhua Tang; Yanping Wang; Lei Wu (Journal of Fish Biology, 2023)
Small yellow croaker ( Larimichthys polyactis ), a commercially essential fish commonly caught in China and South Korea, is now facing a severe decline in resources. The recruitment and surplus of L. polyactis depend selecting a suitable marine environment for overwintering. However, the international overwintering migration habit of L. polyactis limits the investigation of its overwintering environment preferences and suitable grounds. In this study, based on the distribution data of L. polyactis in the southern Yellow Sea in winter from 2010 to 2019 and ocean remote sensing data such as sea bottom temperature (SBT), sea bottom salinity, chlorophyll‐a concentration and water depth (Depth), we used the maximum entropy (MaxEnt) and the genetic algorithm for rule‐set production (GARP) models to investigate the overwintering grounds of the southern Yellow Sea stock (SYS). The jackknife test was used to assess the importance of various environmental factors. For modelling the overwintering ground distribution of SYS, the area under the curve values of both models ​were higher than 0.9. The overwintering ground was at 32°10′ N–33°48′ N, 122°30′ E–125°00′ E. The direction of its distribution was consistent with the Yellow Sea Warm Current in the southern Yellow Sea during the winter. Compared with the suitable overwintering area during 2010–2014, the highly appropriate overwintering area for SYS to overwinter decreased significantly during 2015–2019, showing a trend of moving to the east and north, related to the increase in fishing pressure and strengthening of the Yellow Sea Warm Current in recent years. Depth was the most significant factor for SYS overwintering, followed by SBT. The overwintering ground was at a depth of 40–65 m during the two periods. Additionally, the suitability of overwintering grounds in the coastal waters of south‐western South Korea has gradually increased. This study provides a scientific basis for formulating effective strategies to manage L. polyactis resources under the China–South Korea Fisheries Agreement.

Relationships between Abyssal Redox Conditions and Rock Magnetic Properties of Surficial Sediments in the Western Pacific - Yanping Chen; Dong Xu; Huafeng Qin; Geng Liu; Yibing Li; Weiwei Chen; Liang Yi (Journal of Marine Science and Engineering, 2023)
Reconstructing changes in deep/bottom-water redox conditions are critical for understanding the role of the deep ocean in global carbon and metals cycling; nevertheless, the quantitative relationships between redox proxies and abyssal dissolved oxygen are poorly investigated. In this work, we studied the rock magnetic properties of surficial sediments in the western Pacific to investigate their relationship with regional redox conditions. Our results reveal a consistent sedimentary magnetic mineral assemblage in the western Pacific, dominated by pseudo-single-domain magnetite (Fe3O4), while the ratio of detrital and biogenic magnetite particles in different sites varies substantially. Detailed analyses identified two major magnetic-coercivity components, with modal coercivity values of 13.1 ± 1.6 mT and 54.7 ± 5.3 mT, respectively. All the magnetic parameters we measured, including both concentration-dependent and grainsize-dependent parameters, and the magnetic coercivities, are generally correlated to sedimentary redox conditions; however, the coercivities obtained by mathematical unmixing exhibit a stronger linkage, explaining about a quarter of variance of redox changes. Our findings confirm the potential of magnetic properties for tracing abyssal redox changes in the western Pacific, while the observed magnetic-redox relationships are complex and need further investigation.

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

Enhanced degradation of tetracycline under natural sunlight through the synergistic effect of Ag3PO4/MIL-101(Fe) photocatalysis and Fenton catalysis: Mechanism, pathway, and toxicity assessment - Xiaojuan Chen; Liang Yao; Juhua He; Jiesen Li; Song Xu; Ning Li; Yanping Zhu; Xin Chen; Runliang Zhu (Journal of Hazardous Materials, 2023)

Modeling EDTA-facilitated cadmium migration in high- and low-permeability systems using MODFLOW and RT3D - Xueji You; Shuguang Liu; Somayeh G. Esfahani; Yanping Duan; Jixiang Li; Chaomeng Dai; Charles J. Werth (Journal of Contaminant Hydrology, 2023)

The effect of in vitro digestion on the chemical and antioxidant properties of Lycium barbarum polysaccharides - Wenjun Zeng; Lulu Chen; Yanping Li; Jianlong Ma; Rui Yang; Jianbao Ding; Jin Yang (Food Hydrocolloids, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Ag3PO4-anchored La2Ti2O7 nanorod as a Z-Scheme heterostructure composite with boosted photogenerated carrier separation and enhanced photocatalytic performance under natural sunlight - Xiaojuan Chen; Jieming Chen; Ning Li; Jiesen Li; Juhua He; Song Xu; Yanping Zhu; Liang Yao; Yiqi Lai; Runliang Zhu (Environmental Pollution, 2023)

Revisiting the biological pathway for methanogenesis in landfill from metagenomic perspective—A case study of county-level sanitary landfill of domestic waste in North China plain - Qiuling Dang; Xinyu Zhao; Yanping Li; Beidou Xi (Environmental Research, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Calycosin-7-glucoside promotes mitochondria-mediated apoptosis in hepatocellular carcinoma by targeting thioredoxin 1 to regulate oxidative stress - Xiaodong Wei; Yanping Zeng; Fancheng Meng; Tingpu Wang; Hebin Wang; Yijun Yuan; Dongmei Li; Yue Zhao (Chemico-Biological Interactions, 2023)

The evolution of precipitation and its physical mechanisms in arid and humid regions of the Tibetan Plateau - Guiping Li; Zhongbo Yu; Yanping Li; Zhenhua Li; Qin Ju; Ya Huang (Atmospheric Research, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

Ca2+-dependent TaCCD1 cooperates with TaSAUR215 to enhance plasma membrane H+-ATPase activity and alkali stress tolerance by inhibiting PP2C-mediated dephosphorylation of TaHA2 in wheat - Minghan Cui; Yanping Li; Jianhang Li; Fengxiang Yin; Xiangyu Chen; Lumin Qin; Lin Wei; Guangmin Xia; Shuwei Liu (Molecular Plant, 2023)

Multi-color solid-state photoluminescence from orthogonally multi-stimuli-responsive organic molecule for advanced information storage and encryption - Qi Zhang; Li Yang; Yanfei Gao; Yanping Xiang; Hongjuan Li; Shiguo Sun; Yongqian Xu (Chemical Engineering Journal, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

Melatonin Antagonizes Cytokinin Responses to Stimulate Root Growth in Arabidopsis - Yanping Wang; Jinzhu Li; Li Yang; Zhulong Chan (Journal of Plant Growth Regulation, 2023)

Studies of interspecific backcross between hybrids of (Crassostrea angulata ♀ × C. gigas ♂) and their two parental species - Gongpengyang Shi; Yanping Qin; Weitao Wan; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Yunqing Li; Yinyin Zhou; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Microbial reduction of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Chuling Guo; Siyu Zhang; Yanping Deng; Xiaofei Li; Yuancheng Li; Guining Lu; Fei Ling; Zhi Dang (Science of The Total Environment, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

One-step self-assembly of multilayer graphene oxide via streamlined click reactions for sensitive colorimetric assays - Yanfeng Gao; Yanping Wang; Xinli Liu; Zhenxing Zhu; Zhun Li; Zhibin Zhang; Yi Yin; William Chi Shing Cho; Yujun Song; Yuzhen Wang (Analytica Chimica Acta, 2023)

Climate and management impacts on the spatiotemporal dynamics of water-carbon fluxes in the North China Plain - Xingwang Wang; Huimin Lei; Jiadi Li; Yanping Qu; Dongdong Kong; Zailin Huo (Agriculture, Ecosystems & Environment, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Comparative analysis of growth, survival and sex proportion among tetraploid-based autotriploid (Crassostrea gigas and C. angulata) and their allotriploid oysters - Yanping Qin; Gongpengyang Shi; Weitao Wan; Shengyong Li; Yunqing Li; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Feasibility of interspecific hybridization between Iwagaki oyster, Crassostrea nippona and Portuguese oyster, Crassostrea angulata - Shengyong Li; Yanping Qin; Gongpengyang Shi; Weitao Wan; Qingliang Liao; Haitao Ma; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2023)

Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2023)

Eukaryotic community succession on discarded face masks in the marine environment - Jie Ma; Fengyuan Chen; Zhen Zhang; Yanping Li; Jingli Liu; Ciara Chun Chen; Ke Pan (Science of The Total Environment, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Catalytic ozonation mechanisms of Norfloxacin using Cu–CuFe2O4 - Lanhe Zhang; Yiran Li; Jingbo Guo; Zhongfeng Kan; Yanping Jia (Environmental Research, 2023)

S-scheme MIL-101(Fe) octahedrons modified Bi2WO6 microspheres for photocatalytic decontamination of Cr(VI) and tetracycline hydrochloride: Synergistic insights, reaction pathways, and toxicity analysis - Shijie Li; Chunchun Wang; Yanping Liu; Yazi Liu; Mingjie Cai; Wei Zhao; Xiaoguang Duan (Chemical Engineering Journal, 2023)

Bioinspired, stable adhesive Ti3C2Tx MXene-based coatings towards fire warning, smoke suppression and VOCs removal smart wood - Yin Zhang; Yanping Huang; Mei-Chun Li; Shuai Zhang; Weimin Zhou; Changtong Mei; Mingzhu Pan (Chemical Engineering Journal, 2023)

Untargeted Metabolomic Analysis Reveals the Metabolic Disturbances and Exacerbation of Oxidative Stress in the Cerebral Cortex of a BTBR Mouse Model of Autism - Can Cao; Qi Li; Yanping Chen; Mingyang Zou; Caihong Sun; Xiangning Li; Lijie Wu (Journal of Molecular Neuroscience, 2023)

An integrative approach for identification of smoking-related genes involving bladder cancer - Fang Gao; Huiqin Li; Zhenguang Mao; Yanping Xiao; Mulong Du; Shizhi Wang; Rui Zheng; Zhengdong Zhang; Meilin Wang (Archives of Toxicology, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

Carbonate dynamics in a tropical coastal system in the South China Sea featuring upwelling, river plumes and submarine groundwater discharge - Wei Yang; Xianghui Guo; Zhimian Cao; Jianzhong Su; Liguo Guo; Lifang Wang; Yi Xu; Tao Huang; Yan Li; Yanping Xu; Zhe Wang; Guizhi Wang; et al. (Science China Earth Sciences, 2022)

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Prevalence and risk factors of cardiovascular diseases and psychological distress among female scientists and technicians - Lijun Zhang; Yanping Bao; Guo Li; Shuhui Tao; Meiyan Liu (Journal of Zhejiang University-SCIENCE B, 2022)

Clean technology investment considering synergistic effects: a case from the steel sintering process - Jianxin Guo; Xianchun Tan; Xiaoyan Meng; Yanping Li (Environment, Development and Sustainability, 2022)

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Novel genome sequence of Chinese cavefish ( Triplophysa rosa ) reveals pervasive relaxation of natural selection in cavefish genomes - Qingyuan Zhao; Feng Shao; Yanping Li; Soojin V. Yi; Zuogang Peng (Molecular Ecology, 2022)
All cavefishes, living exclusively in caves across the globe, exhibit similar phenotypic traits, including the characteristic loss of eyes. To understand whether such phenotypic convergence shares similar genomic bases, here we investigated genome‐wide evolutionary signatures of cavefish phenotypes by comparing whole‐genome sequences of three pairs of cavefishes and their surface fish relatives. Notably, we newly sequenced and generated a whole‐genome assembly of the Chinese cavefish Triplophysa rosa . Our comparative analyses revealed several shared features of cavefish genome evolution. Cavefishes had lower mutation rates than their surface fish relatives. In contrast, the ratio of nonsynonymous to synonymous substitutions ( ω ) was significantly elevated in cavefishes compared to in surface fishes, consistent with the relaxation of purifying selection. In addition, cavefish genomes had an increased mutational load, including mutations that alter protein hydrophobicity profiles, which were considered harmful. Interestingly, however, we found no overlap in positively selected genes among different cavefish lineages, indicating that the phenotypic convergence in cavefishes was not caused by positive selection of the same sets of genes. Analyses of previously identified candidate genes associated with cave phenotypes supported this conclusion. Genes belonging to the lipid metabolism functional ontology were under relaxed purifying selection in all cavefish genomes, which may be associated with the nutrient‐poor habitat of cavefishes. Our work reveals previously uncharacterized patterns of cavefish genome evolution and provides comparative insights into the evolution of cave‐associated phenotypic traits.

The impact of international technical cooperation in new energy industry on carbon emissions: evidence from the top 30 countries in the global innovation index - Huajie Xu; Yanping Zhou; Huiying Chen; Jing Li; Yuanyuan Kou (Environmental Science and Pollution Research, 2022)

Molecular phylogeny and divergence time estimates for native giant clams (Cardiidae: Tridacninae) in the Asia-Pacific: Evidence from mitochondrial genomes and nuclear 18S rRNA genes - Haitao Ma; Dongmei Yu; Jun Li; Yanping Qin; Yang Zhang; Zhiming Xiang; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2022)
Giant clams are conspicuous bivalves that inhabit in coral reefs. Among the giant clams, eight species of subfamily Tridacninae are the most common in the Asia-Pacific. However, very little is known about their evolutionary history. Here, we determined the complete mitochondria genome of Hippopus porcellanus , which was 29,434 bp in size and contained 13 protein-coding genes, 2 rRNAs and 23 tRNAs. The A+T composition of protein-coding regions was 57.99%, and the AT composition of the 3 rd codon position was 59.33%, of which in agreement with the invertebrate bias favoring codons ending in A or T. Analysis of phylogenetic relationships according to the concatenated nucleotide data set containing 18S rRNA gene and 13 protein-coding genes, the phylogenetic relationship was analyzed by Maximum likelihood and Bayesian inference methods. The results showed that T. maxima was placed with the clade comprising T. noae , T. squamosa , and T. crocea , in which T. squamosa was highly similar to T. crocea and is consistent with the results of the previous studies using15 mitochondrial markers and nuclear 18S rRNA. Moreover, the inferred divergence time of Tridacnidae species is generally consistent with the fossil record of Tridacnidae. The divergence time of H. porcellanus and H. hippopus was about 10.64 Mya, this result is in agreement with the speculation that H. porcellanus also originated in Miocene. The availability of molecular phylogeny and divergence time estimation provides information genetic relationship of Tridacninae, which could be helpful to the ecological research and conservation of giant clams.

Gene–environment interaction between circadian clock gene polymorphisms and job stress on the risk of sleep disturbances - Yuxi Wang; Min Zhao; Peixin Li; Chuancheng Wu; Yanping Lv; Yu Jiang (Psychopharmacology, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Practical research on improving nano majors students' social adaptability by quality development course - Yi Li; Shijun Xu; Cong Zeng; Yanping Yang (Nanotechnology for Environmental Engineering, 2022)

Genome-wide identification of chicken bursae of Fabricius miRNAs in response to very virulent infectious bursal disease virus - Xuewei Huang; Yue Li; Xiaona Wang; Junyan Zhang; Li Wang; Han Zhou; Yanping Jiang; Wen Cui; Xinyuan Qiao; Yijing Li; Lijie Tang (Archives of Virology, 2022)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Toxicity and Bioaccumulation of Copper in Phaeodactylum tricornutum Under Different Macronutrient Conditions - Beibei Zhou; Yue Zou; Jie Ma; Yanping Li; Ke Pan (Frontiers in Marine Science, 2022)
In this study, we investigated cell physiological and biochemical responses to copper (Cu) accumulation in the marine diatom Phaeodactylum tricornutum under different nitrogen (N) and phosphorus (P) conditions. Cells with sufficient N and P (+N+P) showed the highest total Cu concentrations and displayed a higher metal-tolerance ability. In the +N+P treatments, 36.5% of dissolved Cu was adsorbed on the frustules (cell walls), 54.9% was occluded in organelles, and 8.6% was in the soluble fraction. In comparison, cells with N and/or P shortages (+N−P, −N+P, and −N−P) adsorbed 10.8–13.1% of the total Cu onto their cell walls, 74.5–80% was occluded in organelles, and 9.2–12.4% was in the soluble fraction. The Cu 2+ influx on the +N+P cell wall was faster due to sufficient metal ligands on the cell walls and up-regulated metal-related transporters. A significant increase in protein content occurred under N and/or P shortages, which was accompanied by the inhibition of the antioxidative enzymatic system and cell membrane damage. Our findings indicate that N and P play an important role in both Cu adsorption (cell surface) and uptake (intracellular), and they provide multifaceted evidence of the Cu acquisition mechanism in P. tricornutum under different macronutrient conditions.

HrreNet: semantic segmentation network for moderate and high-resolution satellite images - Yanping Li; Lu Wang; Lei Zhang; Haiwen Chen; Shiying Wang; Xiaoying Wang (International Journal of Remote Sensing, 2022)

Early-Holocene Paleo-Tropical Cyclone Activity Inferred from a Sedimentary Sequence in South Yellow Sea, East Asia - Geng Liu; Xibin Han; Yanping Chen; Jun Li; Lehui Song; Xin Zhou; Bangqi Hu; Liang Yi (Journal of Earth Science, 2022)

Poor evidence for host-dependent regular RNA editing in the transcriptome of SARS-CoV-2 - Jinbao Zong; Yanping Zhang; Fenfen Guo; Changyuan Wang; Hong Li; Gaoyang Lin; Wenqing Jiang; Xiaoping Song; Xiufang Zhang; Feng Huang; Min Qi; Xin Zheng (Journal of Applied Genetics, 2022)

Study on the Individual Coloring Mechanism of Iridescent Cells in the Mantle of the Boring Giant Clam, Tridacna crocea - Yunqing Li; Yinyin Zhou; Jinkuan Wei; Gongpengyang Shi; Qingliang Liao; Shuming Guo; Zihua Zhou; Jun Li; Yanping Qin; Haitao Ma; Ziniu Yu; Yuehuan Zhang (Frontiers in Marine Science, 2022)
Giant clams are marine bivalves that inhabit Indo-Pacific coral reefs. The boring giant clam, Tridacna crocea , exhibits bright and conspicuous mantle coloration based on the specialized cells (iridocytes) that generate structural colors. In order to illustrate the coloring mechanism of individual iridocytes, the reflection spectra curve of iridocytes was obtained by a micro-hyperspectral imager. TEM images were obtained to show the inner nanostructures of iridocytes. FDTD simulation was conducted to analyze the relationship between the color of iridocytes and the unique lamellar structure. We found that the laminae in the regular arrangement within cells govern the coloration of individual iridocytes. With the gradual increase of lamellar thickness and spacing, the color of the structure varies from bright violet to orange-red, forming a full visible spectrum. This study provides a new understanding of the various colors produced by individual iridocytes.

Dopaminergic Neurons in the Ventral Tegmental–Prelimbic Pathway Promote the Emergence of Rats from Sevoflurane Anesthesia - Yanping Song; Ruitong Chu; Fuyang Cao; Yanfeng Wang; Yanhong Liu; Jiangbei Cao; Yongxin Guo; Weidong Mi; Li Tong (Neuroscience Bulletin, 2022)

Analyses of the circadian clock genes expression in whole embryos and maternal major tissues of mice - Ximei Cao; Yindi Yan; Xuguang Luo; Xinhua Yang; Huilin Cui; Yanping Yang; Hairong Li (Journal of Molecular Histology, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Octahedral silver oxide nanoparticles enabling remarkable SERS activity for detecting circulating tumor cells - Meng He; Jie Lin; Ozioma Udochukwu Akakuru; Xiawei Xu; Yanying Li; Yi Cao; Yanping Xu; Aiguo Wu (Science China Life Sciences, 2022)

Synchronous removal of tetracycline and copper (II) over Z‑scheme BiVO4/rGO/g-C3N4 photocatalyst under visible-light irradiation - Jiangli Sun; Yiyuan Rong; Yanping Hou; Lingli Tu; Qingyu Wang; Yuying Mo; Shuxuan Zheng; Zan Li; Zuji Li; Zebin Yu (Environmental Science and Pollution Research, 2022)

Thiamine induces resistance in tobacco against black shank - Tian Suohui; Chen Yanping; Zi Shuhui; Li Zhihua; Jin Honggang; Liu Jun; Liu Tao (Australasian Plant Pathology, 2022)

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Optimization of a Cable Support Strategy for Roadways in Coal Mines by Using the PSO Algorithm - Zhu Tang; Shuqing Li; Fei Huang; Junwei Yang; Fuling Yang; Yanping Zhu; Dangzheng Yang; Nan Wen (Geotechnical and Geological Engineering, 2022)

What drives green development in China: public pressure or the willingness of local government? - Zhengda Li; Yihan Hou; Junli Cao; Yanping Ding; Xiaoling Yuan (Environmental Science and Pollution Research, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

Recombinant Avian β-Defensin Produced by Food-Grade Lactococcus as a Novel and Potent Immunological Enhancer Adjuvant for Avian Vaccine - Tingting Wang; Zhihao Wang; Jielan Mi; Wenqian Wang; Kai Li; Xiaole Qi; Yulong Gao; Li Gao; Changjun Liu; Yanping Zhang; Qing Pan; Xiaomei Wang; et al. (Probiotics and Antimicrobial Proteins, 2021)
In this study, we expressed rAvBD1-2–6-13 protein through Lactococcus lactis NZ3900, and the effects of the recombinant L. lactis NZ3900 as an immune enhancer and immune adjuvant were verified using in vivo and in vitro tests. In vitro tests revealed that recombinant L. lactis NZ3900 significantly activated the NF-κB signaling pathway and IRF signaling pathway in J774-Dual™ report cells and significantly increased the transcript levels of IL-10, IL-12p70, CD80, and CD86 in chicken PBMCs and chicken HD11 cells. In vivo experiments revealed that the immunized group supplemented with recombinant L. lactis NZ3900 as an adjuvant had significantly higher serum antibody titers and higher proliferative activity of PBMCs in the blood of the chickens immunized with NDV live and inactivated vaccines. Our study shows that the recombinant L. lactis NZ3900 has strong immunomodulatory activity both in vivo and in vitro and is a potential immune enhancer. Our work lays the foundation for the research and development of new animal immune enhancers for application in the poultry industry.

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Assessing risk to human health for heavy metal contamination from public point utility through ground dust: a case study in Nantong, China - Yanping Wang; Peng Qian; Dongming Li; Haifeng Chen; Xiangqian Zhou (Environmental Science and Pollution Research, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Tetraploid induction of Crassostrea hongkongensis and C. sikamea by inhibiting the polar body 1 release in diploid fertilized eggs - Yanping Qin; Zohaib Noor; Xingyou Li; Haitao Ma; Jun Li; Yinyin Zhou; Riguan Mo; Yuehuan Zhang; Ziniu Yu (Marine Life Science & Technology, 2021)

Impact of MtrA on phosphate metabolism genes and the response to altered phosphate conditions in Streptomyces - Yanping Zhu; Peipei Zhang; Ting Lu; Xinyuan Wang; Aiying Li; Yinhua Lu; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2021)
Summary Phosphate metabolism is known to be regulated by the PhoPR regulatory system in Streptomyces and some other bacteria. In this study, we report that MtrA also regulates phosphate metabolism in Streptomyces . Our data showed that, in Streptomyces coelicolor , MtrA regulates not only phosphate metabolism genes such as phoA but also phoP under different phosphate conditions, including growth on rich complex media without added inorganic phosphate and on defined media with low or high concentrations of inorganic phosphate. Cross‐regulation was also observed among mtrA , phoP and glnR under these conditions. We demonstrated both in vitro and in vivo binding of MtrA to the promoter regions of genes associated with phosphate metabolism and to the intergenic region between phoR and phoU , indicating that these phosphate metabolism genes are targets of MtrA. We further showed that MtrA in S . lividans and S . venezuelae has detectable regulatory effects on expression of phosphate metabolism genes. Additionally, the MtrA homologue from Corynebacterium glutamicum bound predicted MtrA sites of multiple phosphate metabolism genes, implying its potential for regulating phosphate metabolism in this species. Overall, our findings support MtrA as a major regulator for phosphate metabolism in Streptomyces and also potentially in other actinobacteria.

Correction to: Dryline characteristics in North America’s historical and future climates - Lucia Scaff; Andreas F. Prein; Yanping Li; Adam J. Clark; Sebastian A. Krogh; Neil Taylor; Changhai Liu; Roy M. Rasmussen; Kyoko Ikeda; Zhenhua Li (Climate Dynamics, 2021)

Dryline characteristics in North America’s historical and future climates - Lucia Scaff; Andreas F. Prein; Yanping Li; Adam J. Clark; Sebastian A. Krogh; Neil Taylor; Changhai Liu; Roy M. Rasmussen; Kyoko Ikeda; Zhenhua Li (Climate Dynamics, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

A semi-supervised learning method for hyperspectral imagery based on self-training and local-based affinity propagation - Haimiao Ge; Haizhu Pan; Liguo Wang; Cheng Li; Yanzhong Liu; Wenlong Zhu; Yanping Teng (International Journal of Remote Sensing, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

A Significant Genetic Admixture in Farmed Populations of the Noble Scallop Chlamys nobilis Revealed by Microsatellite DNA Analysis in Southern China - Haitao Ma; Dongmei Yu; Shu Xiao; Yanping Qin; Yang Zhang; Jun Li; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2021)
The noble scallop, Chlamys nobilis , is an important bivalve mollusk with high commercial value and is usually farmed in the waters of southern China. To date, very little is known about the genetic diversity and population structure of C. nobilis . In this study, 10 microsatellite loci of four farmed C. nobilis populations were compared with one another and compared wild population in southern China. A total of 83 alleles were found. Surprisingly, the level of genetic diversity of the farmed C. nobilis populations was higher than that of the wild population. Although the population genetic of wild population was completely in the Hardy–Weinberg equilibrium, due to heterozygote deficiency, significant deviations from the Hardy–Weinberg equilibrium were found in all farmed populations, suggesting a genetic admixture caused by the mixing of seeds from various hatcheries. The Fst and AMOVA values showed significant genetic differences between wild and farmed populations. The Bayesian assignment also confirmed that genetic admixture was significant and widespread in artificial breeding of C. nobilis . Furthermore, the UPGMA tree topology and PCA demonstrated that the genetic diversity of wild population can be clearly distinguished from farmed populations. In a nutshell, the findings of this study not only fill the knowledge gaps in genetic diversity of wild and farmed C. nobilis populations, but also serve as a guide for maintaining the genetic diversity of C. nobilis in both farmed and wild populations.

Therapeutic efficacy of chitosan nanoparticles loaded with BCG-polysaccharide nucleic acid and ovalbumin on airway inflammation in asthmatic mice - Wentao Yang; Zhaohui Dong; Yujing Li; Yingying Zhang; Huanqin Fu; Yanping Xie (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Junjie Wang; Zihua Zhou; Haitao Ma; Jun Li; Yanping Qin; Jinkuan Wei; Xingyou Li; Qingliang Liao; Yunqing Li; Gongpengyang Shi; Yinyin Zhou; Yuehuan Zhang; et al. (Frontiers in Marine Science, 2021)
According to the RGB law display, the polymorphism of the giant clam mantle color pattern is through four iridocytes. The boring giant clam ( Tridacna crocea ) exhibits diverse mantle colors, including blue, green, purple, gold, and orange. In order to evaluate the genetic laws driving these mantle color patterns, a complete diallel cross between two color strains [blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes)] was performed. Using a single-to-single mating system, two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were produced in triplicates. Higher fertilization rate and hatching rate were observed in all experimental groups, suggesting that there was no sperm–egg recognition barrier between the two strains. In the grow-out stage, the size of the reciprocal hybrids was larger than that of the two pure strains with a degree of heterosis. In addition, compared with the two pure strains, the hybrids have higher larval metamorphosis rate and higher survival rate. At 1 year of age, the mantle color pattern of pure strains showed 100% stable inheritance, while the reciprocal hybrids exhibited colorful patterns (a combination of blue, yellow, and green), suggesting that there was a genetic recombination of the mantle colors during the stable expression period. These results provide a theoretical basis for the formation of the mantle color of giant clam and its genetic segregation law, as well as provide guidance for genetic breeding of giant clams.

Genome-wide analysis of ARF transcription factors reveals HcARF5 expression profile associated with the biosynthesis of β-ocimene synthase in Hedychium coronarium - Farhat Abbas; Yanguo Ke; Yiwei Zhou; Yunyi Yu; Muhammad Waseem; Umair Ashraf; Xinyue Li; Rangcai Yu; Yanping Fan (Plant Cell Reports, 2021)

Overexpression of KcNHX1 gene confers tolerance to multiple abiotic stresses in Arabidopsis thaliana - Yanqin Wang; Yuan Guo; Fen Li; Yanping Liu; Shuangxia Jin (Journal of Plant Research, 2021)

Characterization of a novel brain cell line from Jian carp (Cyprinus carpio var. Jian) - Ying Li; Yanping Ma; Le Hao; Jiangyao Ma; Zhiling Liang; Zhenxing Liu; Hao Ke; Yugu Li (Fish Physiology and Biochemistry, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effects of Symbiodiniaceae Phylotypes in Clades A–E on Progeny Performance of Two Giant Clams (Tridacna squamosa and T. crocea) During Early History Life Stages in the South China Sea - Chao Long; Yuehuan Zhang; Yunqing Li; Jun Li; Zihua Zhou; Yanping Qin; Xingyou Li; Haitao Ma; Jinkuan Wei; Yinyin Zhou; Zohaib Noor; Lijuan Long; et al. (Frontiers in Marine Science, 2021)
Unlike most bivalves, giant clams (tridacnids) harbor symbiotic microalgae (zooxanthellae) in their other fleshy bodies. The effects of mixed populations of zooxanthellae on larval metamorphosis has been reported in several papers, but there have been very few studies on the effects of single zooxanthella species on the establishment of symbiosis in giant clams. In this study, we obtained five pure zooxanthella species (clades A3, B1, C1, D1, E1) from antler coral by molecular identification, and analyzed their effects on the larval metamorphosis and progeny performance of two giant clams, Tridacna squamosa and T. crocea , in the South China Sea. Clam larvae with all five zooxanthella species underwent larval settlement and metamorphosis, and formed the zooxanthellal tubular system. There was some variation in metamorphic rate and time to metamorphosis between clams with different zooxanthella species, but no significant differences in size at metamorphosis. After metamorphosis, larvae with all zooxanthella types continued to develop normally. Mantle color was consistent within clam species and zooxanthella species had no effect on mantle color. However, clam progeny with clade E1 zooxanthellae were smaller than progeny with the other four zooxanthella clades (A3, B1, C1, and D1). Survival rate was over 90% for all progeny and there were no significant differences in survival between progeny with Symbiodinium clades A–E during the entire culture process. Two-way ANOVA analysis revealed that giant clam species was the main factor influencing progeny growth, with some variation in growth attributable to zooxanthella type. Our results provide new information on both the symbiotic relationship between giant clams and zooxanthellae and the mantle coloration of giant clams, and will be useful in giant clam seed production and aquaculture.

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Research on the Establishment and Application of the Environmental Health Indicator System of Atmospheric Pollution in China - Qiong Wang; Liangzhong Li; Yanping Zhang; Qian Cui; Yuanzheng Fu; Wanying Shi; Qin Wang; Dongqun Xu (Bulletin of Environmental Contamination and Toxicology, 2021)

Using Statistical and Dynamical Downscaling to Assess Climate Change Impacts on Mine Reclamation Cover Water Balances - Md. Shahabul Alam; S. Lee Barbour; Mingbin Huang; Yanping Li (Mine Water and the Environment, 2020)

Object-based tracking of precipitation systems in western Canada: the importance of temporal resolution of source data - Lintao Li; Yanping Li; Zhenhua Li (Climate Dynamics, 2020)

Comparative analysis of the gut microbiota of grass carp fed with chicken faeces - Famin Ke; Yanping Gao; Li Liu; Chun Zhang; Qin Wang; Xiaowei Gao (Environmental Science and Pollution Research, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Simulating the convective precipitation diurnal cycle in North America’s current and future climate - Lucia Scaff; Andreas F. Prein; Yanping Li; Changhai Liu; Roy Rasmussen; Kyoko Ikeda (Climate Dynamics, 2020)

Evaluation of convection-permitting WRF CONUS simulation on the relationship between soil moisture and heatwaves - Zhe Zhang; Yanping Li; Fei Chen; Michael Barlage; Zhenhua Li (Climate Dynamics, 2020)

Bacillus amyloliquefaciens Ameliorates H2O2-Induced Oxidative Damage by Regulating Transporters, Tight Junctions, and Apoptosis Gene Expression in Cell Line IPEC-1 - Yanping Wu; Han Xu; Xuefang Cao; Rongrong Liu; Li Tang; Zhonghua Zeng; Weifen Li (Probiotics and Antimicrobial Proteins, 2020)

First Case of Rhinocerebral Mucormycosis Caused by Lichtheimia ornata, with a Review of Lichtheimia Infections - Junling Pan; Clement Tsui; Mengxing Li; Kun Xiao; G. Sybren de Hoog; Paul E. Verweij; Yu Cao; Hongguang Lu; Yanping Jiang (Mycopathologia, 2020)

Cloning and functional analysis of the calreticulin gene from the scleractinian coral Galaxea astreata - Yuanjia Huang; Yanping Zhang; Huipai Peng; Jigui Yuan; Li Liu (Acta Oceanologica Sinica, 2020)

Effect of arrangement and quantity of epipremnum aureum on work efficiency and subjective perceptions - Lijun Zuo; Dan Wu; Yanping Yuan; Hanlin Li; Le Yu (Environmental Science and Pollution Research, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Using 4-km WRF CONUS simulations to assess impacts of the surface coupling strength on regional climate simulation - Liang Chen; Yanping Li; Fei Chen; Michael Barlage; Zhe Zhang; Zhenhua Li (Climate Dynamics, 2019)

The Growth Rate, Immune Status, Duodenal Development, and Cecal Microbial Diversity of 24-Day-Old Offspring of SD Rats Received Bacillus subtilis-Cu or CuSO4 During Pregnancy and Lactation Periods - Guodong Liu; Baowei Wang; Yanping Huang; Kailing Li; Wenhua Ge; Mingai Zhang; Bin Yue; Min Kong (Biological Trace Element Research, 2019)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Inheritance and Molecular Marker for Flowering Time in Radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Li Zhang (Plant Molecular Biology Reporter, 2018)

Probiotic Properties and Cellular Antioxidant Activity of Lactobacillus plantarum MA2 Isolated from Tibetan Kefir Grains - Wei Tang; Chao Li; Zengguo He; Fen Pan; Shuo Pan; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Dioxin-like polychlorinated biphenyls in marine fish from Shandong, China, and human dietary exposure - Yanping Cao; Dafeng Jiang; Fenghua Li; Jindong Chen; Wei Li; Yanni Jiao; Lu Li (Food Additives & Contaminants Part B-Surveillance, 2018)

Improved isolation of cadmium from paddy soil by novel technology based on pore water drainage with graphite-contained electro-kinetic geosynthetics - Xianqiang Tang; Qingyun Li; Zhenhua Wang; Yanping Hu; Yuan Hu; Miklas Scholz (Environmental Science and Pollution Research, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Soil dissimilatory nitrate reduction processes in the Spartina alterniflora invasion chronosequences of a coastal wetland of southeastern China: Dynamics and environmental implications - Dengzhou Gao; Xiaofei Li; Xianbiao Lin; Dianming Wu; Baoshi Jin; Yanping Huang; Min Liu; Xing Chen (Plant and Soil, 2017)

Recent land cover changes and sensitivity of the model simulations to various land cover datasets for China - Liang Chen; Zhuguo Ma; Rezaul Mahmood; Tianbao Zhao; Zhenhua Li; Yanping Li (Meteorology and Atmospheric Physics, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Recovering missing pixels for Landsat ETM + SLC-off imagery using HJ-1A /1B as auxiliary data - Chang Li; Yanping Zheng; Yijin Wu (International Journal of Remote Sensing, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

Br/Cl, I/Cl and chlorine isotopic compositions of pore water in shallow sediments: implications for the fluid sources in the Dongsha area, northern South China Sea - Yanping Li; Shaoyong Jiang; Tao Yang (Acta Oceanologica Sinica, 2017)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Cycloartane-type triterpenoids from Astragalus hoantchy French. - Kai Guo; Xiaofeng He; Dengxue Lu; Yanping Zhang; Xiuzhuang Li; Zhiqiang Yan; Bo Qin (Natural Product Research, 2017)

Circulation characteristics of persistent cold spells in central–eastern North America - Zhenhua Li; Alan H. Manson; Yanping Li; Chris Meek (Journal of Meteorological Research, 2017)

Social and environmental influences on tartary buckwheat (Fagopyrum tataricum Gaertn.) varietal diversity in Yunnan, China - Mary Saunders Bulan; Jiangchong Wu; Eve Emshwiller; Mark E. Berres; Joshua L. Posner; Duoyi Peng; Xinhui Wang; Junfang Li; David E. Stoltenberg; Yanping Zhang (Genetic Resources and Crop Evolution, 2017)

Expression of lycopene biosynthesis genes fused in line with Shine-Dalgarno sequences improves the stress-tolerance of Lactococcus lactis - Xiangrong Dong; Yanping Wang; Fengyuan Yang; Shanshan Zhao; Bing Tian; Tao Li (Biotechnology Letters, 2017)

Disturbance of chlorophyll biosynthesis at Mg branch affects the chloroplast ROS homeostasis and Ca2+ signaling in Pisum sativum - Sha Luo; Tao Luo; Peng Peng; Yanping Li; Xiaogang Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Characterization of eleven microsatellite markers for the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) - Shengli Jing; Baoxiao Zheng; Li Qiao; Kun Zhang; Gaoyang Chen; Shunqin Guo; Xiaoyan Huang; Yanping Gao; Lili Zhang; Hongyu Yuan (Applied Entomology and Zoology, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Genetic diversity of gliadin in Secale cereale subsp. segetale from Xinjiang, China - Yonghe Che; Ming Dai; Yanping Yang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2016)

A single mutation in the PBC loop of VP2 is involved in the in vitro replication of infectious bursal disease virus - Xiaole Qi; Xiang Gao; Zhen Lu; Lizhou Zhang; Yongqiang Wang; Li Gao; Yulong Gao; Kai Li; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; et al. (Science China Life Sciences, 2016)

Environmental behaviors of phenolic acids dominated their rhizodeposition in boreal poplar plantation forest soils - Yanping Wang; Chuanrong Li; Qingkui Wang; Huatian Wang; Baoli Duan; Guangcan Zhang (Journal of Soils and Sediments, 2016)

Down-Regulation of ClC-3 Expression Reduces Epidermal Stem Cell Migration by Inhibiting Volume-Activated Chloride Currents - Rui Guo; Fuqiang Pan; Yanping Tian; Hongli Li; Shirong Li; Chuan Cao (The Journal of Membrane Biology, 2016)

A Comprehensive Analysis of Carotenoid Cleavage Dioxygenases Genes in Solanum Lycopersicum - Yanping Wei; Hongjian Wan; Zhiming Wu; Rongqing Wang; Meiying Ruan; Qingjing Ye; Zhimiao Li; Guozhi Zhou; Zhuping Yao; Yuejian Yang (Plant Molecular Biology Reporter, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Pharmacodynamics and Pharmacokinetics of Levobupivacaine Used for Epidural Anesthesia in Patients with Liver Dysfunction - Juhong Ran; Yanping Wang; Fangkun Li; Wei Zhang; Minyu Ma (Cell Biochemistry and Biophysics, 2015)

Isolation and Characterization of a Novel Virulent Phage of Lactobacillus casei ATCC 393 - Xi Zhang; Yu Lan; Wenchao Jiao; Yijing Li; Lijie Tang; Yanping Jiang; Wen Cui; Xinyuan Qiao (Food and Environmental Virology, 2015)

Insights into tetracycline adsorption onto kaolinite and montmorillonite: experiments and modeling - Yanping Zhao; Xueyuan Gu; Shiyin Li; Ruiming Han; Guoxiang Wang (Environmental Science and Pollution Research, 2015)

Biological Modulation of Mouse RPE Cells in Response to Subthreshold Diode Micropulse Laser Treatment - Zhouyue Li; Yanping Song; Xiao Chen; Zhongshan Chen; Qin Ding (Cell Biochemistry and Biophysics, 2015)

Evidence of the Matthew effect in scientific research on mammals in the Chinese First-class National Protected Animals list - He Zhang; Yanping Hu; Yanming Zhang; Wenjing Li (Biodiversity and Conservation, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Characterization of porcine skeletal α-actin gene promoter: expression specificity and regulatory elements - Yujie Zhang; Xu Zhang; Nini Cheng; Yanping Li; Jinyi Xing (Genes & Genomics, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Erythropoietin (EPO) Protects Against High Glucose-Induced Apoptosis in Retinal Ganglional Cells - Yunxiao Wang; Hui Zhang; Yanping Liu; Ping Li; Zhihong Cao; Yu Cao (Cell Biochemistry and Biophysics, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

Intake of fruit and vegetables and risk of bladder cancer: a dose–response meta-analysis of observational studies - Baodong Yao; Yujie Yan; Xianwu Ye; Hong Fang; Huilin Xu; Yinan Liu; Sheran Li; Yanping Zhao (Cancer Causes & Control, 2014)

The association between C-159T polymorphism in CD14 gene and susceptibility to tuberculosis: a meta-analysis - Qing Yuan; Huifang Chen; Xueyan Zheng; Xiaming Chen; Qun Li; Yanping Zhang; Xiaorong Zhang; Tingli Shi; Junhua Zhou; Qing Chen; Shouyi Yu (Molecular Biology Reports, 2014)

Orexin A attenuates the sleep-promoting effect of adenosine in the lateral hypothalamus of rats - Yanping Cun; Lin Tang; Jie Yan; Chao He; Yang Li; Zhian Hu; Jianxia Xia (Neuroscience Bulletin, 2014)

Composition and spectroscopic characteristics of dissolved organic matter extracted from the sediment of Erhai Lake in China - Yanping Li; Shengrui Wang; Li Zhang; Haichao Zhao; Lixin Jiao; Yali Zhao; Xiaosong He (Journal of Soils and Sediments, 2014)

Overexpression of CDK5 in Neural Stem Cells Facilitates Maturation of Embryonic Neurocytes Derived from Rats In Vitro - Hongyu Quan; Xiyan Wu; Yanping Tian; Yun Wang; Chengren Li; Hongli Li (Cell Biochemistry and Biophysics, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Contrasting patterns of river runoff and sea-ice melted water in the Canada Basin - Jinlu Tong; Min Chen; Yusheng Qiu; Yanping Li; Jianping Cao (Acta Oceanologica Sinica, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

The structural characteristics of precipitation in Asian-Pacific’s three monsoon regions measured by tropical rainfall measurement mission - Jiangnan Li; Yanping Zheng; Fangzhou Li; Feiyun Guo; Weibiao Li (Acta Oceanologica Sinica, 2014)

Study of the Mechanism of Bystander Effect of KDR-CDglyTK System Mediated by Adenovirus for the Treatment of Gastric Cancer - Li Qiang; Li Yanping; Huang Zonghai; Chen Fei; Li Zhou; Yu Jinlong (Cell Biochemistry and Biophysics, 2013)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Sciadopitysin: active component from Taxus chinensis for anti-Alzheimer's disease - Qiong Gu; Yanping Li; Yingchun Chen; Peifen Yao; Tianmiao Ou (Natural Product Research, 2013)

Dopamine transporter availability in heroin-dependent subjects and controls: longitudinal changes during abstinence and the effects of Jitai tablets treatment - Ying Liu; Mei Han; Xingdang Liu; Yanping Deng; Yu Li; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Jinlong Gao (Psychopharmacology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Therapy with Astragalus polysaccharides rescues lipotoxic cardiomyopathy in MHC-PPARα mice - Wei Chen; Wenjie Chen; Yanping Xia; Xuelan Zhao; Hao Wang; Maohua Yu; Yiming Li; Hongying Ye; Yu Zhang (Molecular Biology Reports, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Expression of biologically active human interferon alpha 2b in the milk of transgenic mice - Hui Li; Qingyou Liu; Kuiqing Cui; Jinfeng Liu; Yanping Ren; Deshun Shi (Transgenic Research, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Soil Respiration and N2O Flux Response to UV-B Radiation and Straw Incorporation in a Soybean–Winter Wheat Rotation System - Zhenghua Hu; Hailing Cui; Shutao Chen; Shuanghe Shen; Hanmao Li; Yanping Yang; Cenzi Li (Water, Air, & Soil Pollution, 2013)

RETRACTED ARTICLE: Isolation and analysis of homoeologous genes encoding gibberellin 2-oxidase 3 isozymes in common wheat - QIUFANG CHEN; HUIYUAN YA; SHIMING LI; YANPING YANG; GUANGYONG QIN; XUELI AN; DAOWEN WANG; KUNPU ZHANG; ZHEN JIAO (Journal of Genetics, 2012)

Molecular cloning, expression profile, polymorphism and the genetic effects of the dopamine D1 receptor gene on duck reproductive traits - Cui Wang; Shijun Li; Chuang Li; Yanping Feng; Xiuli Peng; Yanzhang Gong (Molecular Biology Reports, 2012)

Identification of microRNA-like RNAs in a plant pathogenic fungus Sclerotinia sclerotiorum by high-throughput sequencing - Jiahong Zhou; Yanping Fu; Jiatao Xie; Bo Li; Daohong Jiang; Guoqing Li; Jiasen Cheng (Molecular Genetics and Genomics, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

Identification and analysis of the gene cluster involved in biosynthesis of paenibactin, a catecholate siderophore produced by Paenibacillus elgii B69 - Yanping Wen; Xuechang Wu; Yi Teng; Chaodong Qian; Zhajun Zhan; Yuhua Zhao; Ou Li (Environmental Microbiology, 2011)
Summary Bacteria belonging to the genus Paenibacillus are recognized as rich sources of bioactive natural products. To date, there are few characterized siderophores from this genus. Here, through genome analysis, we identified a non‐ribosomal peptide biosynthetic gene cluster ( pae ) responsible for siderophore assembly in Paenibacillus elgii B69. The 12.8 kb gene cluster comprises six open reading frames encoding proteins similar to the components of the bacillibactin biosynthetic machinery and bacillibactin esterase. To examine the product of the pae gene cluster, we cultured P. elgii B69 in iron‐deficient medium for siderophore expression. A novel siderophore structurally similar to bacillibactin, designated paenibactin, was purified and characterized. Its structure was determined as a cyclic trimeric lactone of 2,3‐dihydroxybenzoyl‐alanine‐threonine. The involvement of the pae gene cluster in paenibactin biosynthesis was confirmed by the biochemical assay of adenylation domain specificity. Furthermore, we demonstrated that the pae gene cluster evolves from an ancestral bacillibactin biosynthetic gene cluster via sequence and phylogenetic analyses. The structural difference between paenibactin and bacillibactin may stem from a mutation‐induced change in the adenylation domain specificity. Based on these findings and published models for bacillibactin, we proposed models for paenibactin biosynthesis, ferric–paenibactin uptake and paenibactin‐bounded iron release.

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

RNA interference-mediated silencing of iASPP induces cell proliferation inhibition and G0/G1 cell cycle arrest in U251 human glioblastoma cells - Guilin Li; Renzhi Wang; Jun Gao; Kan Deng; Junji Wei; Yanping Wei (Molecular and Cellular Biochemistry, 2011)

Molecular Cloning and Expression Analysis of a Terpene Synthase Gene, HcTPS2, in Hedychium coronarium - Ruihong Li; Yanping Fan (Plant Molecular Biology Reporter, 2011)

Genetical and molecular analysis reveals a cooperating relationship between cytoplasmic male sterility- and fertility restoration-related genes in Oryza species - YanPing Tan; ShaoQing Li; HongWei Xie; ShiHua Duan; Ting Wang; YingGuo Zhu (Theoretical and Applied Genetics, 2011)

Single nucleotide polymorphism of FSHβ gene associated with reproductive traits in Japanese flounder (Paralichthys olivaceus) - Feng He; Haishen Wen; Dahui Yu; Jifang Li; Bao Shi; Caifang Chen; Jiaren Zhang; Guoxiong Jin; Xiaoyan Chen; Dan Shi; Yanping Yang (Journal of Ocean University of China, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

Brief report: a new profile of terminal N-acetyllactosamines glycans on pig red blood cells and different expression of α-galactose on Sika deer red blood cells and nucleated cells - Yingxia Tan; Feng Gong; Subo Li; Shouping Ji; Yanping Lu; Hongwei Gao; Hua Xu; Yangpei Zhang (Glycoconjugate Journal, 2010)

Nucleotide diversity and molecular evolution of the PSY1 gene in Zea mays compared to some other grass species - Zhiyuan Fu; Jianbing Yan; Yanping Zheng; Marilyn L. Warburton; Jonathan H. Crouch; Jian-Sheng Li (Theoretical and Applied Genetics, 2010)

Utilization of microbial iron assimilation processes for the development of new antibiotics and inspiration for the design of new anticancer agents - Marvin J. Miller; Helen Zhu; Yanping Xu; Chunrui Wu; Andrew J. Walz; Anne Vergne; John M. Roosenberg; Garrett Moraski; Albert A. Minnick; Julia McKee-Dolence; Jingdan Hu; Kelley Fennell; et al. (BioMetals, 2009)

Gametophytically alloplasmic CMS line of rice (Oryza sativa L.) with variant orfH79 haplotype corresponds to specific fertility restorer - Shaoqing Li; Yanping Tan; Kun Wang; Cuixiang Wan; Yingguo Zhu (Theoretical and Applied Genetics, 2008)

Antifungal substances produced by Penicillium oxalicum strain PY-1—potential antibiotics against plant pathogenic fungi - Liping Yang; Jiatao Xie; Daohong Jiang; Yanping Fu; Guoqing Li; Fangcan Lin (World Journal of Microbiology and Biotechnology, 2008)

Alteration of integrin-associated protein (CD47) on experimental porcine eperythrozoonosis - Wei Li; Ning Du; Binrui Xu; Weixing Dong; Zhe Qu; Yong Wang; Yanping Sui (Veterinary Research Communications, 2008)

Endothelial cytoskeletal elements are critical for flow-mediated dilation in human coronary arterioles - Yanping Liu; Hongwei Li; Aaron H. Bubolz; David X. Zhang; David D. Gutterman (Medical & Biological Engineering & Computing, 2008)

Overexpression of SBPase enhances photosynthesis against high temperature stress in transgenic rice plants - Lingling Feng; Kun Wang; Yang Li; Yanping Tan; Jin Kong; Hui Li; Yangsheng Li; Yingguo Zhu (Plant Cell Reports, 2007)

Impacts of climatic factors on runoff coefficients in source regions of the Huanghe River - Liqun Chen; Changming Liu; Yanping Li; Guoqiang Wang (Chinese Geographical Science, 2007)

BAPTA blocks DNA fragmentation and chromatin condensation downstream of caspase-3 and DFF activation in HT-induced apoptosis in HL-60 cells - Min Zhang; Yanping Li; Hongqing Zhang; Shaobai Xue (Apoptosis, 2001)